B-stage coating film, laminated film, three-dimensional molded body, and their manufacturing method

By forming a wet coating on the membrane base plate, pre-drying and self-clave treatment, the problems of insufficient industrial stability and three-dimensional shape forming capabilities in the manufacturing of B-stage coatings are solved, and high-performance surface hardness, scratch resistance and chemical resistance are achieved.

JP7670624B2Active Publication Date: 2025-04-30RIKEN TECHNOS CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021569807
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-08
Filing Date
2020-12-18
Publication Date
2025-04-30
Estimated Expiration
2040-12-18

AI Technical Summary

Technical Problem

The prior art is difficult to maintain industrial stability when manufacturing B-stage coatings, three-dimensional shape molding capabilities are insufficient, and surface hardness and scratch resistance are poor.

Method used

One method is adopted to form a wet coating on the membrane base plate, pre-dry to form a dry coating, and self-clave treatment at high pressure and suitable temperatures, and finally completely cured after the application of the three-dimensional shape.

Benefits of technology

The industrial stable manufacturing of B-stage coatings has been achieved, the three-dimensional shape forming capacity has been improved, and the surface hardness, scratch resistance and chemical resistance after curing have been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670624000004
    Figure 0007670624000004
  • Figure 0007670624000005
    Figure 0007670624000005
  • Figure 0007670624000006
    Figure 0007670624000006
Patent Text Reader

Abstract

The present invention is a method for producing a B-stage coating film, comprising the steps of: (1) forming a wet coating film on at least one surface of a film base material using a coating material containing (A) an active-energy-ray-curable resin and (B) a photopolymerization initiator; (2) pre-drying the wet coating film formed in step (1) to form a dry coating film; and (3) subjecting the dry coating film formed in step (2) to an autoclave treatment. The method may further include a step of overlaying a protection film on the surface of the dry coating film formed in step (2) and temporality bonding the protection film subsequent to step (2) or prior to step (3). The autoclave treatment in step (3) may be carried out under such a condition that the film is retained under a pressure of 0.15 to 1 MPa at a temperature of 23 to 100°C for 1 to 60 minutes. The method may further include a step of carrying out an aging treatment subsequent to step (3). The coating material may contain (C) microparticles (which may be an antibacterial agent or an antiviral agent).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a B-stage coating film and a method for producing a B-stage coating film. More specifically, the present invention relates to a B-stage coating film, a laminated film, a three-dimensional molded body, and methods for producing these. [Background technology]

[0002] Conventionally, in order to impart functions such as surface hardness and scratch resistance to molded articles such as housings for home appliances and information electronic devices, and instrument panels for automobiles, a curable resin coating such as an acrylic resin, a melamine resin, an isocyanate resin, or a urethane resin has often been applied to the surface of the base of the molded article to form a cured coating film.

[0003] As a method for forming the cured coating film, a method is widely adopted in which the substrate is first molded, and the curable resin coating material is applied and cured on the surface of the substrate by using a method such as dip coating, spray coating, spin coating, and air knife coating. On the other hand, the above method has various problems such as the following, particularly when the substrate has a three-dimensional shape / stereoscopic shape (for example, a shape that is curved as a whole, a shape with unevenness on the surface, etc.), such as it is difficult to apply the curable resin coating material to a uniform thickness on the surface of the substrate; the curable resin coating material flows after application before curing, and the cured coating film is likely to have uneven thickness / poor appearance; and the productivity is insufficient because the coating material is applied to each substrate.

[0004] Therefore, a method has been proposed in which a coating material is applied to the surface of a thermoplastic resin film with good productivity by a roll-to-roll method such as roll coating, gravure coating, reverse coating, and die coating to form a B-stage coating film, and the resulting laminated film is shaped into a predetermined shape by a method such as hot press molding, and then the B-stage coating film is completely cured; and a method has been proposed in which the laminated film is inserted into a mold for injection molding, the laminated film is heated and softened to be shaped into a predetermined shape, and a desired thermoplastic resin is injected into the mold, and then the B-stage coating film is completely cured (see, for example, Patent Documents 1 and 2). However, with these techniques, it is difficult to industrially stably produce a B-stage coating film, and in particular, it is difficult to industrially stably maintain a balance between curing a wet coating film to a B-stage state and keeping the curing of the wet coating film in a B-stage state. In addition, the three-dimensional moldability (the difficulty of occurrence of defective phenomena such as cracking and whitening when a three-dimensional shape is given) when the coating film is in the B stage is insufficient. Furthermore, the surface hardness and scratch resistance after the coating film is completely cured are not fully satisfactory. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2012-521476 [Patent Document 2] JP 2016-221922 A Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a novel method for producing a B-stage coating film. Another object of the present invention is to provide a novel B-stage coating film. A further object of the present invention is to provide a B-stage coating film that is excellent in three-dimensional formability (the resistance to defects such as cracks, fractures, and poor appearance (e.g., whitening) when a three-dimensional shape is imparted), and a method for producing the same. Yet another object of the present invention is to provide a coating film that is excellent in three-dimensional formability in the B stage and excellent in surface hardness, scratch resistance, and chemical resistance after complete curing (in the C stage), a laminated film having the coating film, a molded body containing the coating film or the laminated film, and a method for producing the same. [Means for solving the problem]

[0007] As a result of extensive research, the present inventors have found that the above object can be achieved by a specific method.

[0008] That is, the various aspects of the present invention are as follows. [1]. A method for producing a B-stage coating film, comprising the steps of: (1) forming a wet coating film on at least one surface of a film substrate using a coating material containing (A) an active energy ray-curable resin and (B) a photopolymerization initiator; (2) pre-drying the wet coating film formed in the step (1) to form a dry coating film; and (3) Autoclaving the dried coating film formed in step (2) The above manufacturing method. [2]. The method according to the above item [1], further comprising the step of superposing and temporarily attaching a protective film on the surface of the dried coating film formed in step (2) after step (2) and before step (3). [3]. The method according to item [1] or [2] above, wherein the autoclave treatment in the step (3) is carried out under conditions of a pressure of 0.15 to 1 MPa, a temperature of 23 to 100° C., and a time of 1 to 60 minutes. [4]. The method according to any one of the above items [1] to [3], further comprising a step of carrying out an aging treatment after the step (3). [5]. The method according to any one of the above items [1] to [4], wherein the coating material further comprises (C) fine particles. [6]. The method according to item [5] above, wherein the component (C) microparticles comprise microparticles that function as an antibacterial agent or an antiviral agent. [7]. The method according to any one of the above items [1] to [6], wherein the coating material further comprises (D) a water repellent. [8]. The method according to any one of the above items [1] to [7], wherein the coating material does not contain a thermal polymerization initiator. [9]. The method according to any one of the above items [1] to [8], wherein the above (A) active energy ray-curable resin contains (A1) urethane (meth)acrylate.

[10] . The method according to any one of the above items [1] to [9], wherein the above (A) active energy ray-curable resin contains (A2) a copolymer of (a1) a multifunctional (meth)acrylate and (a2) a multifunctional thiol.

[11] . The method according to any one of the above items [1] to

[10] , further comprising a step of transferring the autoclaved coating film on the film substrate formed in the step (3) onto a substrate other than the film substrate.

[12] . A method for producing a three-dimensional molded body, comprising the steps of: (P) obtaining a B-stage coating film applied onto the film substrate or a B-stage coating film transferred onto a substrate other than the film substrate by the method according to any one of items [1] to

[11] ; (Q) a step of imparting a three-dimensional shape to the B-stage coating film applied onto the film substrate obtained in the step (P), or the B-stage coating film transferred onto a substrate other than the film substrate; and (R) The above method, which includes a step of completely curing the B-stage coating film that has been given a three-dimensional shape in the above step (Q). Effect of the Invention

[0009] The manufacturing method of the present invention allows the B-stage coating film to be manufactured industrially and stably. The preferred manufacturing method of the present invention allows the B-stage coating film with excellent three-dimensional moldability to be manufactured industrially and stably. The B-stage coating film of the present invention has excellent three-dimensional moldability. The preferred B-stage coating film of the present invention has excellent three-dimensional moldability in the B stage, and after complete curing (in the C stage), has excellent surface hardness, scratch resistance, and chemical resistance. Therefore, the molded body molded using the B-stage coating film of the present invention or the laminated film of the present invention having this B-stage coating film has excellent surface hardness, scratch resistance, and chemical resistance, and also has a good surface appearance (there are no defective phenomena such as cracks, cracks, and poor appearance (e.g., whitening)). Therefore, the B-stage coating film of the present invention or the laminated film of the present invention having this B-stage coating film can be suitably used to impart functions such as surface hardness, scratch resistance, and chemical resistance to the surface of a molded body having a three-dimensional shape / stereoscopic shape, for example, the housing of a home appliance or information electronic device, and an instrument panel of an automobile. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a conceptual diagram showing an example of an apparatus used for temporarily attaching a protective film onto the surface of a dried coating film. [Diagram 2] FIG. 2 is a GPC curve of the component (A1-1) used in the examples. [Diagram 3] FIG. 3 is a GPC curve of the component (A2-1) used in the examples. [Figure 4] FIG. 4 is a conceptual diagram illustrating vacuum forming. [Diagram 5] FIG. 5(a) is a front view and (b) is a plan view of the mold used in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In this specification, the term "resin" is used to include a resin mixture containing two or more resins and a resin composition containing components other than resin. In this specification, the term "film" is used interchangeably or interchangeably with "sheet". In this specification, the terms "film" and "sheet" are used to refer to something that can be industrially wound into a roll. The term "plate" is used to refer to something that cannot be industrially wound into a roll. In this specification, laminating a layer and another layer in order includes both directly laminating the layers and laminating the layers with one or more layers, such as an anchor coat, interposed between the layers.

[0012] In this specification, the term "more than" in relation to a numerical range means a certain number or more than a certain number. For example, 20% or more means 20% or more than 20%. The term "less than" in relation to a numerical range means a certain number or less than a certain number. For example, 20% or less means 20% or less than 20%. Furthermore, the symbol "~" in relation to a numerical range means a certain number, more than a certain number and less than another certain number, or another certain number. Here, the other certain number is a number larger than the certain number. For example, 10 to 90% means 10%, more than 10% and less than 90%, or 90%. Furthermore, the upper and lower limits of the numerical range can be arbitrarily combined, and an embodiment in which the values ​​are arbitrarily combined can be read. For example, from a statement regarding the numerical range of a certain characteristic such as "usually 10% or more, preferably 20% or more. On the other hand, it is usually 40% or less, preferably 30% or less" or "usually 10 to 40%, preferably 20 to 30%," it can be read that the numerical range of the certain characteristic is 10 to 40%, 20 to 30%, 10 to 30%, or 20 to 40% in one embodiment.

[0013] Other than in the examples, or where otherwise specified, all numerical values ​​used in the specification and claims should be understood to be modified by the term "about." Without attempting to limit the application of the doctrine of equivalents to the scope of the claims, each numerical value should be construed in light of the number of significant digits and by applying ordinary rounding techniques.

[0014] In this specification, the term "B stage" is used for thermosetting resins in the sense defined in JIS K6800-1985, that is, "an intermediate curing state of thermosetting resins. In this state, the resin softens when heated and swells when exposed to certain solvents, but does not completely melt or dissolve." For active energy ray curable resins, it is used to mean "an intermediate curing state of active energy ray curable resins. In this state, the resin softens when heated and swells when exposed to certain solvents, but does not completely melt or dissolve."

[0015] In this specification, the term "C stage" is used for both a thermosetting resin and an active energy ray-curable resin in the same sense as defined in JIS K6800-1985, and means "the final state of the curing reaction of a curable resin. The resin in this state is insoluble and infusible. The curable resin in a completely cured coating film is in this state."

[0016] 1. Manufacturing method of B-stage coating The manufacturing method of the present invention includes the steps of: (1) forming a wet coating film on at least one surface of a film substrate using a coating material containing (A) an active energy ray-curable resin and (B) a photopolymerization initiator (hereinafter, sometimes abbreviated as "B-stage coating film-forming coating material"); (2) pre-drying the wet coating film formed in the step (1) to form a dry coating film; and (3) autoclaving the dry coating film formed in the step (2).

[0017] The above step (1) is a step of forming a wet coating film on at least one surface of a film substrate using the above-mentioned B-stage coating film forming paint. The above-mentioned step (1) is usually a step of forming a wet coating film on one surface of the film substrate using the above-mentioned B-stage coating film forming paint.

[0018] The film substrate used in the above step (1) is not particularly limited, and any film can be used as the film substrate. As the film substrate used in the above step (1), the film substrate described in "3. B-stage coating film laminated film" below can be preferably used. As the paint for forming the B-stage coating film used in the above step (1), the paint described in "2. B-stage coating film" below can be preferably used.

[0019] In the step (1), the method of forming a wet coating film on the surface of the film substrate using the coating material for forming a B-stage coating film is not particularly limited, and a known web application method can be used. As the web application method, from the viewpoint of applying the coating material with good productivity by a roll-to-roll method, for example, a method such as rod coating, roll coating, gravure coating, reverse coating, kiss reverse coating, and die coating is preferable.

[0020] The step (2) is a step of pre-drying the wet coating film formed in the step (1) to form a dry coating film. By pre-drying the wet coating film to form the dry coating film, production problems such as foaming of the coating film can be suppressed in the step (3). The pre-drying can be performed, for example, by passing the web through a drying oven usually set at a temperature of about 23 to 150°C, preferably a temperature of 50 to 130°C, more preferably a temperature of 70 to 120°C, at a line speed such that the time required for passing from the inlet to the outlet is about 0.5 to 10 minutes, preferably 1 to 5 minutes.

[0021] After the above step (2) and before the above step (3), it is preferable to temporarily attach a protective film on the surface of the above dried coating film formed in the above step (2). This can prevent manufacturing problems such as scratches on the coating film (dried coating film or B stage coating film) before it is completely cured (to C stage). In addition, after three-dimensional molding, in the process of irradiating the coating film with active energy rays to change it from B stage to C stage, manufacturing problems such as poor curing due to oxygen damage can be prevented.

[0022] An example of a method for temporarily laminating the protective film on the surface of the dried coating film will be described with reference to FIG. 1. FIG. 1 is a conceptual diagram showing an example of an apparatus used for temporarily laminating the protective film on the surface of the dried coating film. The laminate 1 (a laminate having the dried coating film on one surface of the film substrate) obtained in the above step (2) is placed on a rotating drum 3 so that the surface of the laminate 1 opposite to the dried coating film faces the rotating drum 3, and a protective film 2 is placed on the surface of the dried coating film of the laminate 1 and pressed by a pressure roller 4. The laminate 5 in which the protective film 2 is temporarily laminated on the surface of the dried coating film is released from the rotating drum 3 by a guide roller 6 and sent to step (3). The rotating drum 3 may be preheated to a desired temperature. The temperature of the rotating drum 3 may usually be room temperature (about 23° C.) to about 100° C., preferably room temperature (about 23° C.) to about 50° C.

[0023] The protective film is preferably one having active energy ray permeability (hereinafter, sometimes referred to as "active energy ray permeable protective film"). When the B-stage coating film of the present invention is completely cured (to C-stage), active energy rays can be irradiated without peeling off the protective film, so that production troubles can be suppressed. The thickness of the protective film is not particularly limited, but may be, for example, in the range of about 10 μm to about 600 μm, preferably in the range of 20 μm to 250 μm.

[0024] Here, "having active energy ray transparency" means that the active energy ray transmittance of the film is usually 70% or more, preferably 80% or more. In this specification, the active energy ray transmittance is the ratio of the integrated area of ​​the transmission spectrum of active energy rays at wavelengths of 200 to 600 nanometers to the integrated area of ​​the transmission spectrum when the transmittance of active energy rays in the entire range of wavelengths of 200 to 600 nanometers is assumed to be 100%. The transmission spectrum is measured using a spectrophotometer by irradiating light onto the film at an incident angle of 0°. As the spectrophotometer, for example, a spectrophotometer "SolidSpec-3700" (product name) manufactured by Shimadzu Corporation can be used.

[0025] Examples of the active energy ray-transmitting protective film include polyethylene terephthalate-based resin films, polypropylene-based resin films, aromatic polycarbonate-based resin films, and fluorine-containing resin films.

[0026] The surface of the protective film that is bonded to the dry coating film may be treated to facilitate peeling, may not be treated to facilitate peeling, or may be treated to facilitate adhesion. The easy peeling treatment may be any known treatment method, such as forming a peelable layer using a silicone resin or the like. The adhesion enhancing treatment may be any known treatment method such as a corona discharge treatment, a plasma treatment, or the formation of an anchor coat.

[0027] By using a protective film whose surface to be bonded to the dried coating film has been treated for easy peeling, typically a film having an embossed pattern on the bonding surface is used, and even in cases where an embossed pattern is to be formed on the surface of the dried coating film by transferring the shape of the embossed pattern to the dried coating film, production problems that occur when peeling and removing the protective film can be suppressed.

[0028] By using the protective film whose surface to be bonded to the dried coating film has not been subjected to easy peeling treatment, the adhesion between the dried coating film and the protective film can be maintained at a minimum level required for web handling, particularly in the case where the B-stage coating film-forming paint exhibits tack-free properties simply by drying the coating film. Here, "tack-free properties" refers to the resistance to scratches and appearance defects caused by the coating film coming into contact with a transport roll or the like during web handling.

[0029] The use of the protective film having a surface to be bonded to the dried coating film that has been treated for easy adhesion is useful as one embodiment of the case where the film substrate used in the step (1) has a surface on which the B-stage coating film is formed that has been treated for easy peeling. In this case, the B-stage coating film is usually transferred from the film substrate used in the step (1) to the protective film. In this case, it goes without saying that "temporarily attach" can technically be read as "attach and adhere".

[0030] The surface of the protective film to be bonded to the dried coating film may be highly smooth, may be matte, or may have an embossed pattern. By using a protective film having a highly smooth bonding surface, the fully cured (C stage) coating film formed using the B stage coating film of the present invention has a high gloss. By using a protective film having a matte bonding surface, the fully cured (C stage) coating film formed using the B stage coating film of the present invention has a matte (low gloss). By using a protective film having a bonding surface with an embossed pattern, the fully cured (C stage) coating film formed using the B stage coating film of the present invention has an embossed pattern.

[0031] The step (3) is a step of autoclaving the dried coating film formed in the step (2). The step (3) can suppress production troubles such as foaming of the coating film when, for example, a step of imparting a three-dimensional shape to the B-stage coating film of the present invention or a step of completely curing (C-stage) the B-stage coating film of the present invention is produced when a three-dimensional molded product is produced using a laminate having the B-stage coating film of the present invention. In addition, in an embodiment using the protective film, the step (3) can transfer the shape of the bonding surface of the protective film with the dried coating film to the surface of the dried coating film. Furthermore, in an embodiment using the protective film, the step (3) can remove the air even if air is trapped between the protective film and the dried coating film, thereby preventing poor appearance.

[0032] The above step (3) can be carried out by the following procedure. In a typical embodiment, first, the dry coating film formed in the above step (2) (a laminate having the dry coating film on at least one surface of the film substrate; a laminate having the dry coating film on at least one surface of the film substrate, and further having the protective film superposed and temporarily attached on that surface; or a roll of these laminates; the same applies hereinafter in this paragraph) is placed inside an autoclave, and the lid of the autoclave is closed. Next, the inside of the autoclave is heated and pressurized to a predetermined temperature and pressure, and after the temperature and pressure are reached, the temperature and pressure are maintained for a predetermined time (hereinafter sometimes referred to as "retention time"). Subsequently, the pressure is lowered to normal pressure, and preferably the temperature is also lowered to around room temperature, and then the lid of the autoclave is opened, and the dry coating film formed in the above step (2) can be taken out.

[0033] The autoclave apparatus is not particularly limited, and any known autoclave apparatus can be used. The temperature, pressure, and holding time of the autoclave treatment can be appropriately selected in consideration of the characteristics of the paint used in forming the B-stage coating film of the present invention and the film substrate. In an embodiment using the protective film, the temperature, pressure, and holding time of the autoclave treatment can be appropriately selected in consideration of the characteristics of the paint used in forming the B-stage coating film of the present invention, the film substrate, and the protective film. The pressure of the autoclave treatment is usually higher than normal pressure (0.1 MPa), preferably 0.15 to 1 MPa, more preferably 0.2 to 0.7 MPa, and even more preferably 0.3 to 0.6 MPa. The temperature of the autoclave treatment may usually be room temperature (about 23°C) to 100°C, preferably 30 to 80°C, and more preferably 40 to 60°C. The holding time of the autoclave treatment may usually be 1 to 60 minutes, preferably 3 to 30 minutes, and more preferably 5 to 20 minutes.

[0034] It is preferable to carry out an aging treatment after the above step (3). The properties of the B-stage coating film of the present invention can be stabilized. In addition, when a three-dimensional molded product is produced using a laminated film having the B-stage coating film of the present invention, for example, in a step of imparting a three-dimensional shape to the B-stage coating film of the present invention or a step of completely curing (C-stage) the B-stage coating film of the present invention, the risk of production troubles such as foaming of the coating film can be further suppressed. The conditions of the aging treatment are not particularly limited. The temperature of the aging treatment may be usually about 23 to 150°C, preferably 50 to 120°C, and more preferably 70 to 100°C. The time of the aging treatment may be usually about 10 minutes to 10 hours, preferably 30 minutes to 4 hours, and more preferably 1 to 3 hours.

[0035] Without intending to be bound by theory, it is believed that the heat generated during pre-drying in step (2) above; in the embodiment in which the protective film is used, the heat generated when the protective film is superimposed and temporarily attached; the heat and pressure generated during autoclave treatment in step (3) above; and the heat generated during aging treatment (if performed) cause the coating film to gradually harden due to heat, reaching a B-stage state.

[0036] 2. B-stage coating The B-stage coating film of the present invention is formed by any method using the above-mentioned paint for forming a B-stage coating film (a paint containing the above-mentioned component (A) active energy ray curable resin and the above-mentioned component (B) photopolymerization initiator). The B-stage coating film of the present invention is preferably formed by the manufacturing method of the present invention using the above-mentioned paint for forming a B-stage coating film (a paint containing the above-mentioned component (A) active energy ray curable resin and the above-mentioned component (B) photopolymerization initiator). The above-mentioned paint for forming a B-stage coating film (a paint containing the above-mentioned component (A) active energy ray curable resin and the above-mentioned component (B) photopolymerization initiator) will be described below.

[0037] (A) Active energy ray curable resin The above-mentioned component (A), the active energy ray-curable resin, functions to form a coating film by being polymerized and cured by active energy rays such as ultraviolet rays and electron beams.

[0038] Examples of the active energy ray-curable resin of component (A) include (meth)acryloyl group-containing prepolymers or oligomers such as urethane (meth)acrylate (or polyurethane (meth)acrylate), polyester (meth)acrylate, polyacryl (meth)acrylate, epoxy (meth)acrylate, polyalkylene glycol poly(meth)acrylate, and polyether (meth)acrylate.

[0039] Examples of the component (A) active energy ray-curable resin include (meth)acryloyl group-containing monofunctional reactive monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, phenyl (meth)acrylate, phenyl cellosolve (meth)acrylate, 2-methoxyethyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, 2-acryloyloxyethyl hydrogen phthalate, dimethylaminoethyl (meth)acrylate, trifluoroethyl (meth)acrylate, and trimethylsiloxyethyl methacrylate; monofunctional reactive monomers such as N-vinylpyrrolidone and styrene; diethylene glycol di(meth)acrylate, ne Examples of the monomer include (meth)acryloyl group-containing bifunctional reactive monomers such as dipentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 2,2'-bis(4-(meth)acryloyloxypolyethyleneoxyphenyl)propane, and 2,2'-bis(4-(meth)acryloyloxypolypropyleneoxyphenyl)propane; (meth)acryloyl group-containing trifunctional reactive monomers such as trimethylolpropane tri(meth)acrylate and trimethylolethane tri(meth)acrylate; (meth)acryloyl group-containing tetrafunctional reactive monomers such as pentaerythritol tetra(meth)acrylate; (meth)acryloyl group-containing hexafunctional reactive monomers such as dipentaerythritol hexaacrylate; (meth)acryloyl group-containing octafunctional reactive monomers such as tripentaerythritol octaacrylate; and prepolymers or oligomers having one or more of these as constituent monomers.

[0040] Examples of the component (A) active energy ray-curable resin include compounds having two thiol groups in one molecule, such as 1,2-ethanedithiol, ethylene glycol bis(3-mercaptopropionate), diethylene glycol bis(3-mercaptopropionate), 1,4-bis(3-mercaptobutyryloxy)butane, and tetraethylene glycol bis(3-mercaptopropionate); 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylolpropane tris( Examples of the thiol groups include compounds having three thiol groups in one molecule, such as pentaerythritol tetrakis(3-mercaptobutyrate), trimethylolethane tris(3-mercaptobutyrate), and tris[(3-mercaptopropionyloxy)ethyl]isocyanurate; compounds having four thiol groups in one molecule, such as pentaerythritol tetrakis(3-mercaptopropionate) and pentaerythritol tetrakis(3-mercaptobutyrate); and compounds having six thiol groups in one molecule, such as dipentaerythritol hexakis(3-mercaptopropionate).

[0041] The component (A) active energy ray-curable resin may be one of these, a mixture of two or more of these, or a copolymer formed from two or more of these. In this specification, (meth)acrylate means acrylate or methacrylate.

[0042] It is preferable to use an active energy ray curable resin (A) containing an (A1) urethane (meth)acrylate, which can improve in a well-balanced manner the three-dimensional formability of the B-stage coating film, as well as the surface hardness, scratch resistance, and chemical resistance after complete curing (C-stage).

[0043] When the component (A) active energy ray curable resin contains the component (A1) urethane (meth)acrylate, the compounding ratio of the component (A1) may be usually 10% by mass or more, preferably 25% by mass or more, more preferably 40% by mass or more, based on the total of the components (A) being 100% by mass, from the viewpoint of reliably obtaining the effect of using the component (A1). On the other hand, the compounding ratio of the component (A1) may be usually 99% by mass or less, preferably 95% by mass or less, more preferably 93% by mass or less, even more preferably 85% by mass or less, and most preferably 65% ​​by mass or less, based on the viewpoint of surface hardness. When environmental resistance measured according to the environmental tests of the tests (iv) and (v) in the following examples is particularly important, the compounding ratio of the component (A1) may be preferably 65 to 100% by mass, more preferably 75 to 100% by mass, based on the total of the components (A) being 100% by mass.

[0044] It is preferable to use a copolymer of (A2) (a1) polyfunctional (meth)acrylate and (a2) polyfunctional thiol as the component (A) active energy ray curable resin. This can improve the surface hardness, scratch resistance, and chemical resistance after complete curing (at C stage). In addition, in an embodiment in which the B stage coating film of the present invention is formed only on one side of the film substrate, curling and warping of the laminate can be suppressed.

[0045] When the component (A) active energy ray curable resin contains the component (A2) (a1) multifunctional (meth)acrylate and (a2) multifunctional thiol copolymer, the blending ratio of the component (A2) may be usually 1% by mass or more, preferably 5% by mass or more, more preferably 7% by mass or more, based on the total of the components (A) being 100% by mass, from the viewpoint of reliably obtaining the effect of using the component (A2). On the other hand, the blending ratio of the component (A2) may be usually 90% by mass or less, preferably 75% by mass or less, more preferably 60% by mass or less, from the viewpoint of crack resistance after complete curing (at C stage).

[0046] It is more preferable to use the component (A) active energy ray curable resin containing the component (A1) urethane (meth)acrylate and the component (A2) copolymer of the (a1) multifunctional (meth)acrylate and the (a2) multifunctional thiol, which can improve the three-dimensional formability in the B-stage coating film and the surface hardness, scratch resistance, and chemical resistance after complete curing (in the C-stage) in a well-balanced manner.

[0047] When the component (A) active energy ray curable resin contains the component (A1) urethane (meth)acrylate and the component (A2) (a1) multifunctional (meth)acrylate and (a2) multifunctional thiol copolymer, the compounding ratio of the component (A1) to the component (A2) (the mass of the component (A1) / the mass of the component (A2)) may be usually 99 / 1 to 10 / 90, preferably 95 / 5 to 25 / 75, more preferably 93 / 7 to 40 / 60, from the viewpoint of the balance of three-dimensional moldability in the B stage coating film and surface hardness, scratch resistance, and chemical resistance after complete curing (at the C stage). When environmental resistance measured according to the environmental tests of the tests (iv) and (v) in the following examples is particularly important, this compounding ratio may be preferably 99 / 1 to 65 / 35, more preferably 95 / 5 to 75 / 25, and even more preferably 93 / 7 to 75 / 25.

[0048] When the component (A) active energy ray-curable resin contains the component (A1) urethane (meth)acrylate and the component (A2) a copolymer of the polyfunctional (meth)acrylate (a1) and the polyfunctional thiol (a2), the sum of the blending amount of the component (A1) and the blending amount of the component (A2) is, with the total of the component (A) being 100% by mass, from the viewpoints of the balance between the three-dimensional formability in the B-stage coating film and the surface hardness, scratch resistance, and chemical resistance after complete curing (at the C-stage), it may be usually 80% by mass or more, preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98 to 100% by mass.

[0049] (A1) Urethane (meth)acrylate The urethane (meth)acrylate of component (A1) is a compound having a urethane structure (-NH-CO-O-) or a derivative thereof having one or more (meth)acryloyl groups. The urethane (meth)acrylate of component (A1) is not particularly limited, but may typically be one produced using a compound having two or more isocyanate groups (-N=C=O) in one molecule, a polyol compound, and a hydroxyl group-containing (meth)acrylate, i.e., one containing structural units derived from these compounds.

[0050] Examples of the compound having two or more isocyanate groups in one molecule include compounds having two isocyanate groups in one molecule, such as diphenylmethane diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, tolylene diisocyanate, and methylene bis(4-cyclohexyl isocyanate). Other examples of the compound having two or more isocyanate groups in one molecule include polyisocyanates such as a trimethylolpropane adduct of tolylene diisocyanate, a trimethylolpropane adduct of hexamethylene diisocyanate, a trimethylolpropane adduct of isophorone diisocyanate, an isocyanurate of tolylene diisocyanate, an isocyanurate of hexamethylene diisocyanate, an isocyanurate of isophorone diisocyanate, and a biuret of hexamethylene diisocyanate.

[0051] As the compound having two or more isocyanate groups in one molecule, one of these compounds or a mixture of two or more of them can be used.

[0052] Examples of the polyol compound include polyether polyol, polyester polyol, and polycarbonate polyol.

[0053] Examples of the polyether polyol include polyalkylene glycols such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; polyalkylene oxides such as polyethylene oxide and polypropylene oxide; copolymers of ethylene oxide and propylene oxide; copolymers of ethylene oxide and tetrahydrofuran; copolymers of dihydric phenol compounds and polyoxyalkylene glycols; and copolymers of dihydric phenols and one or more alkylene oxides having 2 to 4 carbon atoms (e.g., ethylene oxide, propylene oxide, 1,2-butylene oxide, and 1,4-butylene oxide).

[0054] Examples of the polyester polyol include poly(ethylene adipate), poly(butylene adipate), poly(neopentyl adipate), poly(hexamethylene adipate), poly(butylene azelaate), poly(butylene sebacate), and polycaprolactone.

[0055] Examples of the polycarbonate polyol include poly(butanediol carbonate), poly(hexanediol carbonate), and poly(nonanediol carbonate).

[0056] As the polyol compound, one or a mixture of two or more of these can be used.

[0057] Examples of the hydroxyl group-containing (meth)acrylate include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate; glycol-based (meth)acrylates such as dipropylene glycol (meth)acrylate, polyethylene glycol mono(meth)acrylate, and polypropylene glycol mono(meth)acrylate; glycerin-based (meth)acrylates such as glycerin di(meth)acrylate; modified glycidyl-based (meth)acrylates such as fatty acid-modified glycidyl (meth)acrylate; 2-hydroxyethyl (meth)acrylates such as glycerin di(meth)acrylate; Examples of the acrylates include phosphorus atom-containing (meth)acrylates such as acryloyl phosphate; (meth)acrylic acid adducts of esters or ester derivatives such as 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate; pentaerythritol-based (meth)acrylates such as pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, ethylene oxide-modified pentaerythritol tri(meth)acrylate, and ethylene oxide-modified dipentaerythritol penta(meth)acrylate; and caprolactone-modified (meth)acrylates such as caprolactone-modified 2-hydroxyethyl (meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, and caprolactone-modified dipentaerythritol penta(meth)acrylate.

[0058] As the hydroxyl group-containing (meth)acrylate, one of these or a mixture of two or more of them can be used.

[0059] The polystyrene-equivalent number average molecular weight (Mn) of the urethane (meth)acrylate of component (A1) determined from a differential molecular weight distribution curve (hereinafter sometimes abbreviated as "GPC curve") measured by gel permeation chromatography (hereinafter sometimes abbreviated as "GPC curve") may be usually 500 or more, preferably 1000 or more, from the viewpoint of three-dimensional moldability and, in an embodiment in which the protective film is used, from the viewpoint of maintaining the adhesion between the dried coating film and the protective film at a minimum level required for web handling. On the other hand, from the viewpoint of coatability, this number average molecular weight (Mn) may be usually 30,000 or less, preferably 20,000 or less.

[0060] The polystyrene-equivalent mass average molecular weight (Mw) of the urethane (meth)acrylate of the component (A1) determined from a GPC curve measured by GPC may be usually 1000 or more, preferably 2000 or more, from the viewpoint of three-dimensional moldability and, in an embodiment in which the protective film is used, from the viewpoint of maintaining the adhesion between the dried coating film and the protective film at a minimum level required for web handling. On the other hand, from the viewpoint of coatability, this mass average molecular weight (Mw) may be usually 100,000 or less, preferably 50,000 or less.

[0061] The number of (meth)acryloyl groups in the urethane (meth)acrylate of the above component (A1) may be usually 2 or more, preferably 3 or more, per 1000 of the number average molecular weight (Mn) calculated in terms of polystyrene from the GPC curve, from the viewpoint of web handling property and from the viewpoint of surface hardness, scratch resistance, and chemical resistance after complete curing (at C stage). On the other hand, from the viewpoint of three-dimensional moldability, the number of (meth)acryloyl groups may be usually 20 or less, preferably 12 or less, more preferably 10 or less. As described above, the web handling property here means the resistance to scratches and poor appearance caused by the coating film coming into contact with a transfer roll or the like during web handling.

[0062] The polystyrene-equivalent Z-average molecular weight (Mz) of the urethane (meth)acrylate of the component (A1) determined from a GPC curve measured by GPC may be usually 1500 or more, preferably 2500 or more, from the viewpoint of three-dimensional moldability and, in an embodiment in which the protective film is used, from the viewpoint of maintaining the adhesion between the dried coating film and the protective film at a minimum level required for web handling. On the other hand, from the viewpoint of coatability, this Z-average molecular weight (Mz) may be usually 150,000 or less, preferably 100,000 or less.

[0063] The measurement of GPC was performed using a high-performance liquid chromatography system "HLC-8320" (trade name) of Tosoh Corporation as a system (a system including a degasser, a liquid delivery pump, an autosampler, a column oven, and an RI (differential refractive index) detector); as GPC columns, two "KF-806L" (trade name) GPC columns of Shodex, one "KF-802" (trade name) and one "KF-801" (trade name) were connected in the order of KF-806L, KF-806L, KF-802, and KF-801 from the upstream side and used; tetrahydrofuran (without stabilizer) for high-performance liquid chromatography of Wako Pure Chemical Industries, Ltd. was used as the mobile phase; it can be carried out under the conditions of a flow rate of 1.0 milliliter / minute, a column temperature of 40°C, a sample concentration of 1 milligram / milliliter, and a sample injection volume of 100 microliters. The elution amount at each retention volume can be determined from the detection amount of the RI detector on the assumption that the molecular weight dependence of the refractive index of the measurement sample is absent. Also, a calibration curve from the retention volume to the polystyrene-equivalent molecular weight can be created using commercially available standard polystyrene. It should be noted that the standard polystyrene should be appropriately selected so that the measured value is interpolated in the calibration curve. As the analysis program, "TOSOH HLC-8320GPC EcoSEC" (trade name) of Tosoh Corporation can be used. Regarding the theory of GPC and the actual measurement, reference books such as "Size Exclusion Chromatography, High-Performance Liquid Chromatography of Polymers" (author: Sadao Mori, first edition, first printing on December 10, 1991) by Kyoritsu Shuppan Co., Ltd., and "Synthetic Polymer Chromatography" (editors: Hajime Ohtani, Tatsuya Takasaki (the upper part of "崎" is "立"), first edition, first printing on July 25, 2013) by Ohmsha, Ltd. can be referred to.

[0064] FIG. 2 shows the differential molecular weight distribution curve of the following component (A1-1) used in the examples. Two sharp peaks are observed in the relatively low molecular weight region, and the polystyrene-equivalent molecular weights at the peak top positions are 280 and 610, respectively, from the low molecular weight side. A peak of the main component is observed on the high molecular weight side of these two peaks, and the polystyrene-equivalent molecular weight at the peak top position is 2400. The total number average molecular weight (Mn) is 1000, the mass average molecular weight (Mw) is 2900, and the Z-average molecular weight (Mz) is 4700. In addition, since the number of (meth)acryloyl groups per molecule is two, the number of (meth)acryloyl groups per 1000 of polystyrene-equivalent number average molecular weight (Mn) obtained from the GPC curve is two.

[0065] (A2) (a1) Copolymer of multifunctional (meth)acrylate and (a2) multifunctional thiol The component (A2) is a copolymer of (a1) a polyfunctional (meth)acrylate and (a2) a polyfunctional thiol. Since both the components (a1) and (a2) are polyfunctional monomers, the component (A2) is usually a copolymer having a highly branched structure, a so-called dendrimer structure.

[0066] The polyfunctional (meth)acrylate of component (a1) is a (meth)acrylate having two or more (meth)acryloyl groups in one molecule. The number of (meth)acryloyl groups in one molecule of component (a1) may be preferably 3 or more, more preferably 4 or more, and even more preferably 5 or more, from the viewpoint of making the structure of the copolymer of component (A2) have a so-called dendrimer structure. On the other hand, from the viewpoint of crack resistance after complete curing of the coating film (at C stage), the number may be usually 20 or less, preferably 12 or less.

[0067] Examples of the polyfunctional (meth)acrylate of the component (a1) include (meth)acryloyl group-containing bifunctional reactive monomers such as diethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 2,2'-bis(4-(meth)acryloyloxypolyethyleneoxyphenyl)propane, and 2,2'-bis(4-(meth)acryloyloxypolypropyleneoxyphenyl)propane; trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, and ethoxylated trimer tri(meth)acrylate. Examples of such monomers include (meth)acryloyl group-containing trifunctional reactive monomers such as tirolpropane tri(meth)acrylate; (meth)acryloyl group-containing tetrafunctional reactive monomers such as ditrimethylolpropane tetra(meth)acrylate and pentaerythritol tetramethacrylate; (meth)acryloyl group-containing hexafunctional reactive monomers such as dipentaerythritol hexaacrylate; (meth)acryloyl group-containing octafunctional reactive monomers such as tripentaerythritol octaacrylate; and polymers (oligomers or prepolymers) having one or more of these as constituent monomers, and having two or more (meth)acryloyl groups in one molecule. Examples of the component (a1) include prepolymers or oligomers such as polyurethane (meth)acrylate, polyester (meth)acrylate, polyacryl (meth)acrylate, polyepoxy (meth)acrylate, polyalkylene glycol poly(meth)acrylate, and polyether (meth)acrylate, each of which has two or more (meth)acryloyl groups in one molecule. The component (a1) may be one of these or a mixture of two or more of them.

[0068] The polyfunctional thiol of component (a2) is a compound having two or more thiol groups in one molecule. The number of thiol groups in one molecule of component (a2) may be preferably 3 or more, more preferably 4 or more, from the viewpoint of making the structure of the copolymer of component (A2) have a so-called dendrimer structure. On the other hand, from the viewpoint of crack resistance after complete curing of the coating film (at C stage), it may be usually 20 or less, preferably 12 or less. The thiol group of component (a2) may be preferably a secondary thiol group from the viewpoint of the balance between reactivity and handling.

[0069] The above-mentioned component (a2) polyfunctional thiol may have one or more polymerizable functional groups other than thiol groups, such as (meth)acryloyl groups, vinyl groups, epoxy groups, and isocyanate groups, in one molecule. In this specification, a compound having two or more thiol groups and two or more (meth)acryloyl groups in one molecule is classified as the above-mentioned component (a2).

[0070] Examples of the polyfunctional thiol of the component (a2) include compounds having two thiol groups in one molecule, such as 1,2-ethanedithiol, ethylene glycol bis(3-mercaptopropionate), diethylene glycol bis(3-mercaptopropionate), 1,4-bis(3-mercaptobutyryloxy)butane, and tetraethylene glycol bis(3-mercaptopropionate); 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylolpropane tris(3-mercaptobutyrate), trimethylolethane tris(3-mercaptobutyrate), and the like. pentaerythritol tetrakis(3-mercaptobutyrate) and tris[(3-mercaptopropionyloxy)ethyl]isocyanurate, and other compounds having three thiol groups in one molecule; pentaerythritol tetrakis(3-mercaptopropionate) and pentaerythritol tetrakis(3-mercaptobutyrate), and other compounds having four thiol groups in one molecule; dipentaerythritol hexakis(3-mercaptopropionate), and other compounds having six thiol groups in one molecule; and polymers (oligomers and prepolymers) having one or more of these as constituent monomers and having two or more thiol groups in one molecule. As the component (a2), one or a mixture of two or more of these can be used.

[0071] The component (A2) copolymer may contain, in addition to the component (a1) polyfunctional (meth)acrylate and the component (a2) polyfunctional thiol, a structural unit derived from a monomer copolymerizable therewith, to the extent that it does not deviate from the object of the present invention. The copolymerizable monomer is usually a compound having a carbon-carbon double bond, typically a compound having an ethylenic double bond.

[0072] The content of the structural unit derived from the component (a1) polyfunctional (meth)acrylate in the component (A2) copolymer (hereinafter sometimes abbreviated as "(a1) content") may be usually 50 mol% or more, preferably 60 mol% or more, more preferably 70 mol% or more, and even more preferably 80 mol% or more, based on the sum of the structural units derived from the polymerizable monomer being 100 mol%, from the viewpoint of making the structure of the component (A2) copolymer have a so-called dendrimer structure and from the viewpoint of scratch resistance. On the other hand, from the viewpoint of making the structure of the component (A2) copolymer have a so-called dendrimer structure and from the viewpoint of crack resistance and handleability after the coating film is completely cured (at C stage), it may be usually 99 mol% or less, preferably 97 mol% or less, more preferably 95 mol% or less, and even more preferably 93 mol% or less.

[0073] The content of the constituent units derived from the polyfunctional thiol (a2) in the copolymer of component (A2) (hereinafter sometimes abbreviated as "(a2) content") may be usually 1 mol% or more, preferably 3 mol% or more, more preferably 5 mol% or more, and even more preferably 7 mol% or more, based on the sum of the constituent units derived from the polymerizable monomer being 100 mol%, from the viewpoint of making the structure of the component (A) have a so-called dendrimer structure, and from the viewpoint of crack resistance and handleability after the coating film is completely cured (at C stage). On the other hand, from the viewpoint of making the structure of the copolymer of component (A2) have a so-called dendrimer structure, and from the viewpoint of scratch resistance, it may be usually 50 mol% or less, preferably 40 mol% or less, more preferably 30 mol% or less, and even more preferably 20 mol% or less.

[0074] Here, the sum of the content of the polyfunctional (meth)acrylate (a1) and the content of the polyfunctional thiol (a2) may be usually 80 mol% or more, preferably 90 mol% or more, more preferably 95 mol% or more, and even more preferably 99 mol% or more and 100 mol% or less, based on the total of the constitutional units derived from the polymerizable monomer being 100 mol%. The term "polymerizable monomer" means the above component (a1), the above component (a2), and a monomer copolymerizable therewith. The copolymerizable monomer is usually a compound having a carbon-carbon double bond, typically a compound having an ethylenic double bond.

[0075] The sulfur content in the component (A2) copolymer may be usually 0.1 to 12 mass%, preferably 0.5 to 10 mass%, more preferably 1 to 7 mass%, and even more preferably 1.5 to 5 mass%, from the viewpoint of setting the content of the polyfunctional thiol (a2) in the above-mentioned preferred range.

[0076] Here, the sulfur content is a value measured by atomic absorption spectrometry using a microwave device, a mixed acid of nitric acid and hydrochloric acid (volume ratio 8:2) to incinerate the sample (wet decomposition), add an aqueous hydrochloric acid solution, filter, and adjust the volume of the filtrate with purified water to obtain a measurement sample. In this case, yttrium is used as an internal standard. In addition, since sulfur is likely to combine with iron and the like and precipitate, it is important to prevent this. Specifically, the sulfur content can be measured in the same manner as the method described in paragraphs 0035 to 0039 of JP 2018-187924 A.

[0077] The polystyrene-equivalent mass average molecular weight (Mw) of the component (A2) copolymer determined from a GPC curve measured by GPC may be preferably 5,000 or more, more preferably 8,000 or more, and even more preferably 10,000 or more, from the viewpoint of the balance between scratch resistance and crack resistance after the coating film is completely cured (at C stage). On the other hand, this mass average molecular weight (Mw) may be preferably 200,000 or less, more preferably 100,000 or less, and even more preferably 50,000 or less, from the viewpoint of the coatability of a coating material containing the component (A2) copolymer.

[0078] The polystyrene-equivalent Z-average molecular weight (Mz) of the component (A2) copolymer determined from the GPC curve may be preferably 5,000 or more, more preferably 10,000 or more, and even more preferably 30,000 or more, from the viewpoint of the balance between scratch resistance and crack resistance after the coating film is completely cured (at C stage). On the other hand, from the viewpoint of the coatability of the coating material containing the component (A2) copolymer, this Z-average molecular weight (Mz) may be preferably 200,000 or less, more preferably 150,000 or less, and even more preferably 120,000 or less.

[0079] The polystyrene-equivalent number average molecular weight (Mn) of the component (A2) copolymer determined from the GPC curve may be preferably 300 or more, more preferably 500 or more, from the viewpoint of the balance between scratch resistance and crack resistance after the coating film is completely cured (at C stage). On the other hand, from the viewpoint of the coatability of a coating material containing the component (A2) copolymer, this number average molecular weight (Mn) may be preferably 100,000 or less, more preferably 50,000 or less, and even more preferably 20,000 or less.

[0080] The GPC measurement of the component (A2) copolymer can be carried out in the same manner as described above in the description of the component (A1).

[0081] Figure 3 shows the differential molecular weight distribution curve of the following component (A2-1) used in the examples. Three clear peaks are observed in the relatively low molecular weight region, and the polystyrene-equivalent molecular weights at the peak top positions are 340, 570, and 970, in order from the low molecular weight side. In addition, multiple overlapping broad peaks are observed on the high molecular weight side of these three peaks, and the polystyrene-equivalent molecular weight of the component on the highest molecular weight side is recognized to be about 200,000. The overall number average molecular weight (Mn) is 940, the mass average molecular weight (Mw) is 12,000, and the Z average molecular weight (Mz) is 73,000.

[0082] (B) Photopolymerization initiator The component (B) photopolymerization initiator is a compound that generates active species such as radicals when irradiated with active energy rays. The component (B) photopolymerization initiator generates active species such as radicals, thereby polymerizing and curing the component (A) active energy ray-curable resin, and completely curing (C stage) the coating film.

[0083] Examples of the component (B) photopolymerization initiator include benzophenone-based compounds such as benzophenone, methyl-o-benzoylbenzoate, 4-methylbenzophenone, 4,4'-bis(diethylamino)benzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, and 2,4,6-trimethylbenzophenone; benzoin-based compounds such as benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzyl methyl ketal; acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, and 2-hydroxy-1-{4 -[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one and other acetophenone-based compounds, α-hydroxyalkylphenone-based compounds, and alkylphenone-based compounds such as acetophenone dimethyl acetal; anthraquinone-based compounds such as methylanthraquinone, 2-ethylanthraquinone, and 2-amylanthraquinone; thioxanthone-based compounds such as thioxanthone, 2,4-diethylthioxanthone, and 2,4-diisopropylthioxanthone; acylphosphine oxide-based compounds; biimidazole compounds; titanocene-based compounds; oxime ester-based compounds; oxime phenyl acetate-based compounds; hydroxyketone-based compounds; triazine-based compounds; and aminobenzoate-based compounds. The term "alkylphenone compound" is defined as a compound having an acetophenone skeleton (benzene ring-CO-alkyl group) or a structure derived from an acetophenone skeleton. Among these alkylphenone compounds, compounds that retain the carbonyl group C=O derived from the acetophenone skeleton correspond to the term "acetophenone compound". In other words, "acetophenone compound" is a subordinate concept that is included in "alkylphenone compound".

[0084] As the component (B) photopolymerization initiator, from the viewpoint of completely curing (C stage) the coating film after three-dimensional molding, a compound that generates radicals by irradiation with active energy rays is preferable. As the component (B) photopolymerization initiator, from the viewpoint of stably maintaining the coating film in a B stage state until three-dimensional molding, an alkylphenone compound such as an acetophenone compound is preferable, and a hydroxyalkylphenone compound (an alkylphenone compound having a hydroxyl group) such as a hydroxyacetophenone compound (an acetophenone compound having a hydroxyl group) is more preferable. In addition, from the viewpoint of suppressing the volatilization of the photopolymerization initiator due to heat during three-dimensional molding, a photopolymerization initiator with low volatility is preferable. Examples of photopolymerization initiators with low volatility include 1-hydroxycyclohexyl-phenyl ketone and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one. As the component (B), one or a mixture of two or more of these can be used.

[0085] The amount of the component (B) photopolymerization initiator may be appropriately selected by comprehensively considering the viewpoints of curing the coating film in a B-stage state, keeping the coating film in a B-stage state, stably maintaining the coating film in a B-stage state until three-dimensional molding, and completely curing (C-stage) after three-dimensional molding. The amount of the component (B) photopolymerization initiator may be usually 1 part by mass or more, preferably 2 parts by mass or more, more preferably 3 parts by mass or more, and even more preferably 4 parts by mass or more, based on 100 parts by mass of the component (A) active energy ray curable resin, from the viewpoint of curing the coating film in a B-stage state and from the viewpoint of completely curing (C-stage) after three-dimensional molding. On the other hand, the amount of the component (B) photopolymerization initiator may be usually 20 parts by mass or less, preferably 15 parts by mass or less, more preferably 12 parts by mass or less, and even more preferably 10 parts by mass or less, based on the viewpoint of keeping the coating film in a B-stage state and stably maintaining the coating film in a B-stage state until three-dimensional molding.

[0086] (C) Fine particles The coating material for forming the B-stage coating film may preferably further contain the fine particles of component (C) The fine particles of component (C) serve to increase the surface hardness of the molded article (the coating film is in the C-stage) obtained by using the B-stage coating film of the present invention.

[0087] The component (C) fine particles may include inorganic fine particles and organic fine particles. Examples of the inorganic fine particles include silica (silicon dioxide), metal oxide fine particles such as aluminum oxide, zirconia, titania, zinc oxide, germanium oxide, indium oxide, tin oxide, indium tin oxide, antimony oxide, and cerium oxide, metal fluoride fine particles such as magnesium fluoride and sodium fluoride, metal sulfide fine particles, metal nitride fine particles, and metal fine particles.

[0088] Examples of the organic fine particles include fine resin particles such as silicone resins, styrene resins, acrylic resins, fluorine resins, polycarbonate resins, ethylene resins, and cured resins of amino compounds and formaldehyde.

[0089] Among these, silica and aluminum oxide fine particles are preferred from the viewpoint of obtaining a higher surface hardness, and silica fine particles are more preferred. Commercially available silica fine particles include Snowtex (trade name) manufactured by Nissan Chemical Industries, Ltd. and Quartron (trade name) manufactured by Fuso Chemical Industries, Ltd.

[0090] It is preferable to use the surface of the fine particles of component (C), particularly when inorganic fine particles are used as component (C), which are treated with a silane coupling agent such as vinylsilane and aminosilane; a titanate coupling agent; an aluminate coupling agent; an organic compound having an ethylenically unsaturated bond group such as (meth)acryloyl group, vinyl group, and allyl group, or a reactive functional group such as an epoxy group; and a surface treatment agent such as fatty acid and fatty acid metal salt. By treating the surface in this way, the dispersibility of the inorganic fine particles in the coating material can be improved and the surface hardness can be increased.

[0091] In one embodiment, the component (C) fine particles may contain fine particles that function as an antibacterial agent or an antiviral agent (hereinafter, may be referred to as "functional fine particles"). By using the functional fine particles as a part or all of the component (C) fine particles (i.e., in an amount of more than 0% by mass to 100% by mass of component (C)), antibacterial and antiviral properties can be imparted to the coating film of the present invention. In an embodiment in which the functional fine particles are used, the proportion of the functional fine particles in the component (C) fine particles may be usually 10% by mass to 100% by mass, preferably 30% by mass to 100% by mass, and more preferably 50% by mass to 100% by mass. Examples of the functional fine particles include inorganic fine particles that function as antibacterial or antiviral agents, such as copper compounds, silver compounds, tin compounds, molybdenum compounds, and zinc compounds (hereinafter sometimes referred to as "functional inorganic fine particles"). Examples of the copper compound include copper(I) compounds such as copper(I) halides, such as copper(I) chloride (CuCl), copper(I) bromide (CuBr), and copper(I) iodide (CuI), and copper(I) thiocyanate (CuSCN); and copper(II) compounds, such as copper(II) carbonate (CuCO), copper(II) oxide (CuO), and copper(II) chloride (CuCl). The silver compound may, for example, be a silver halide compound such as silver(I) iodide (AgI). Examples of the tin compound include tin halide compounds such as tin tetraiodide (SnI4). Examples of the molybdenum compound include molybdenum oxide compounds such as molybdenum oxide (MoO3), molybdenum-silver composite oxide, molybdenum-zinc composite oxide, and molybdenum-copper composite oxide. The zinc compound may be, for example, a zinc oxide compound such as zinc oxide (ZnO). Other examples of the functional fine particles include functional inorganic fine particles such as potassium aluminum sulfate, silver-sodium-hydrogen-zirconium phosphate, silver-magnesium-aluminum phosphate glass (U.S. Food and Drug Administration FCN registration number 433), silver-magnesium-calcium-borate glass (U.S. Food and Drug Administration FCN registration number 432), silver-zinc-magnesium-aluminum-calcium-sodium-borate phosphate glass (U.S. Food and Drug Administration FCN registration number 476), silver-magnesium-sodium-phosphate glass (U.S. Food and Drug Administration FCN registration number 434), silver-magnesium-zinc-aluminum-calcium-sodium-borate phosphate glass (U.S. Food and Drug Administration FCN registration number 1981), silver zeolite (CAS number 0130328-18-6), silver-copper zeolite (CAS number 0130328-19-7), silver-zinc zeolite (CAS number 0130328-20-0), and copper-tin alloy.

[0092] The component (C) fine particles may be one or a mixture of two or more of these. For example, the component (C) fine particles may be one or a mixture of two or more of organic fine particles and inorganic fine particles. For example, the component (C) fine particles may be one or a mixture of two or more of functional fine particles and other fine particles (organic fine particles and / or inorganic fine particles).

[0093] The average particle size of the component (C) fine particles may be usually 300 nm or less, preferably 200 nm or less, more preferably 120 nm or less, from the viewpoint of maintaining the transparency of the coating film and reliably obtaining the hardness improving effect. On the other hand, there is no particular lower limit for the average particle size, but the fine particles that are usually available are at most about 1 nm at the smallest.

[0094] In this specification, the average particle size of the fine particles is the particle size at which the cumulative amount of the smaller particles is 50 mass % in a particle size distribution curve measured by a laser diffraction / scattering method using a laser diffraction / scattering particle size analyzer. As the laser diffraction / scattering particle size analyzer, for example, "MT3200II" (product name) manufactured by Nikkiso Co., Ltd. can be used.

[0095] The amount of the component (C) fine particles is not particularly limited since it is an optional component. The amount of the component (C) fine particles may be appropriately selected from the viewpoint of surface hardness and crack resistance after complete curing (C stage). The amount of the component (C) may be preferably 10 parts by mass or more, more preferably 80 parts by mass or more, even more preferably 120 parts by mass or more, and most preferably 150 parts by mass or more, based on 100 parts by mass of the component (A) active energy ray curable resin, from the viewpoint of surface hardness after complete curing (C stage). On the other hand, the amount of the component (C) fine particles may be preferably 500 parts by mass or less, more preferably 400 parts by mass or less, even more preferably 300 parts by mass or less, and most preferably 250 parts by mass or less, based on the viewpoint of crack resistance after complete curing (C stage).

[0096] In an embodiment in which the component (C) microparticles contain the functional microparticles, the blending amount of the functional microparticles is appropriately determined from the viewpoint of reliably expressing antibacterial and antiviral properties and from the viewpoint of ensuring that the total amount of the component (C) does not exceed the above-mentioned range. The amount of the functional fine particles may be, from the viewpoint of reliably expressing antibacterial and antiviral properties, usually 1 part by mass or more, preferably 4 parts by mass or more, more preferably 7 parts by mass or more, and even more preferably 10 parts by mass or more, relative to 100 parts by mass of the component (A) active energy ray curable resin. On the other hand, the amount of the functional fine particles may be, from the viewpoint of crack resistance after complete curing (C stage), preferably 500 parts by mass or less, more preferably 400 parts by mass or less, even more preferably 300 parts by mass or less, and most preferably 250 parts by mass or less. In another embodiment, the amount of the functional fine particles may be, from the viewpoint described above, 10 parts by mass or more and 200 parts by mass or less, or 10 parts by mass or more and 100 parts by mass or less, or 10 parts by mass or more and 50 parts by mass or less.

[0097] (D) Water repellent The coating material for forming the B-stage coating film may preferably further contain the water repellent (Component (D)). By using the water repellent (Component (D)), it is possible to improve the scratch resistance, dirt adhesion prevention, and dirt wiping removability of the molded article (coating film is in C stage) obtained using the B-stage coating film of the present invention.

[0098] Examples of the water repellent agent of component (D) include wax-based water repellents such as paraffin wax, polyethylene wax, and acrylic-ethylene copolymer wax; silicone-based water repellents such as silicone oil, silicone resin, polydimethylsiloxane, and alkylalkoxysilane; and fluorine-containing water repellents such as fluoropolyether-based water repellents and fluoropolyalkyl-based water repellents.

[0099] Among these, the component (D) water repellent is preferably a fluorine-containing water repellent from the viewpoint of scratch resistance and water repellency, and from the viewpoint of scratch resistance, water repellency, and preventing troubles such as bleeding out of the component (D) by chemically bonding or strongly interacting the component (D) with the component (A) active energy ray curable resin, a fluorine-containing water repellent containing a (meth)acryloyl group (hereinafter sometimes abbreviated as "(meth)acryloyl group-containing fluorine-based water repellent" is more preferable. Here, the (meth)acryloyl group-containing fluorine-based water repellent is a compound having one or more (meth)acryloyl groups in the molecule and having one or more, preferably three or more, more preferably five or more fluorine-carbon bonds in the molecule (typically a structure in which one or more hydrogen atoms of an organic functional group such as a hydrocarbon group are replaced with fluorine atoms) and exhibiting a water repellent function.

[0100] Examples of the (meth)acryloyl group-containing fluorine-based water repellent include (meth)acryloyl group-containing fluoroether-based water repellent, (meth)acryloyl group-containing fluoroalkyl-based water repellent, (meth)acryloyl group-containing fluoroalkenyl-based water repellent, (meth)acryloyl group-containing fluoropolyether-based water repellent, (meth)acryloyl group-containing fluoropolyalkyl-based water repellent, and (meth)acryloyl group-containing fluoropolyalkenyl-based water repellent.

[0101] As the water repellent of the component (D), a (meth)acryloyl group-containing fluoropolyether water repellent (a compound containing a (meth)acryloyl group and a fluoropolyether group in the molecule) is more preferred. As the water repellent of the component (D), a mixture of an acryloyl group-containing fluoropolyether water repellent and a methacryloyl group-containing fluoropolyether water repellent is most preferred from the viewpoint of appropriately adjusting the chemical bond or interaction between the component (D) and the component (A) active energy ray curable resin, maintaining high transparency, exhibiting good scratch resistance and water repellency, and preventing the bleeding out of the component (D).

[0102] As the component (D) water repellent, one or a mixture of two or more of these can be used.

[0103] The amount of the water repellent (D) is not particularly limited since it is an optional component. The amount of the water repellent (D) may be appropriately determined from the viewpoint of improving the scratch resistance, dirt adhesion prevention, and dirt wiping ability after complete curing (C stage). The amount of the water repellent (D) may be usually 0.01 parts by mass or more, preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.2 parts by mass or more, based on 100 parts by mass of the active energy ray curable resin (A) from the viewpoint of obtaining the effect of using the component (D). On the other hand, the amount of the water repellent (D) may be usually 7 parts by mass or less, preferably 4 parts by mass or less, more preferably 2 parts by mass or less, and even more preferably 1 part by mass or less, from the viewpoint of preventing trouble such as bleeding out of the component (D).

[0104] The coating material for forming the B-stage coating film (a coating material containing the active energy ray curable resin (component (A)) and the photopolymerization initiator (component (B))) may contain, as desired, one or more additives such as a compound having two or more isocyanate groups in one molecule, an antistatic agent, a surfactant, a leveling agent, a thixotropic agent, a stain inhibitor, a printability improver, an antioxidant, a weathering stabilizer, a light resistance stabilizer, an ultraviolet absorber, a heat stabilizer, an inorganic particle, an inorganic colorant, an organic particle, an organic colorant, and a dispersant (for example, an amine-based dispersant such as a phosphate ester salt of a high molecular weight copolymer having a polyamine structure), as long as the purpose of the present invention is not violated. The amount of these additives to be used is not particularly limited, but may be, for example, usually 0.001 parts by mass or more relative to 100 parts by mass of the active energy ray curable resin (component (A)) from the viewpoint of obtaining the effect of using the additive, and usually 10 parts by mass or less from the viewpoint of not interfering with the desired effect according to the present invention.

[0105] The B-stage coating film forming paint may preferably not contain a thermal polymerization initiator. By not containing the thermal polymerization initiator in the B-stage coating film forming paint, it becomes easy to keep the coating film formed in the B-stage state and to stably maintain the coating film in the B-stage state until three-dimensional molding is performed. Here, "not containing" means that the thermal polymerization initiator is not intentionally blended. When the thermal polymerization initiator is intentionally blended, it is usually blended in an amount of 0.01 parts by mass or more per 100 parts by mass of the component (A) active energy ray curable resin. Therefore, "the B-stage coating film forming paint does not contain the thermal polymerization initiator" can be rephrased as the content of the thermal polymerization initiator is usually less than 0.01 parts by mass, preferably 0.005 parts by mass or less, more preferably 0.001 parts by mass or less, even more preferably 0.0005 parts by mass or less, and most preferably about 0 parts by mass, per 100 parts by mass of the component (A) active energy ray curable resin.

[0106] The thermal polymerization initiator is a compound that generates active species such as radicals by heating. In this specification, compounds that generate active species such as radicals by irradiation with active energy rays (or light) or by heating are classified as thermal polymerization initiators. Examples of the thermal polymerization initiator include azo compounds such as 2,2'-azobisisobutyronitrile (2,2'-azobis(2-methylpropionitrile)); organic peroxides such as benzoyl peroxide; and benzenesulfonic acid esters such as cyclohexyl p-toluenesulfonate.

[0107] The coating material for forming the B-stage coating film may contain a solvent, if desired, in order to dilute the coating material to a concentration that is easy to apply. The solvent is not particularly limited as long as it does not react with the component (A), the component (B), and other optional components, or catalyze (promote) the self-reaction (including deterioration reaction) of these components. Examples of the solvent include 1-methoxy-2-propanol, ethyl acetate, n-butyl acetate, toluene, methyl ethyl ketone, methyl isobutyl ketone, diacetone alcohol, and acetone. The solvent may be one of these or a mixture of two or more of them.

[0108] The B-stage coating material can be obtained by mixing and stirring these components.

[0109] The thickness of the B-stage coating film of the present invention is not particularly limited. The thickness of the B-stage coating film of the present invention may be usually 0.5 μm or more, preferably 1 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more, from the viewpoint of surface hardness, scratch resistance, and chemical resistance after complete curing (C-stage). On the other hand, the thickness of the B-stage coating film may be usually 100 μm or less, preferably 50 μm or less, more preferably 30 μm or less, and even more preferably 20 μm or less, from the viewpoint of three-dimensional moldability.

[0110] The tensile elongation of the B-stage coating film of the present invention may be, from the viewpoint of three-dimensional moldability, usually 10% or more, preferably 20% or more, more preferably 25% or more, and even more preferably 30% or more. Higher tensile elongation is preferable. Here, the tensile elongation is a value measured in accordance with JIS K7127:1999 using a test piece of type 2 (width 15 mm, total length 150 mm) taken so that the width direction of the B-stage coating film or the laminated film having the B-stage coating film coincides with the tensile direction, under conditions of a gauge length of 50 mm, an initial distance between chucks of 100 mm, and a test speed of 10 mm / min.

[0111] The pencil hardness of the surface of the B-stage coating film of the present invention after complete curing (reduced to C-stage) may usually be H or more (1H or more), preferably 3H or more, more preferably 4H or more, even more preferably 5H or more, and most preferably 6H or more. Higher pencil hardness is preferable. The pencil hardness here is a value measured according to JIS K5600-5-4:1999 under the conditions of a test length of 25 mm and a load of 750 g.

[0112] 3. B-stage coating laminate film The B-stage coating laminated film of the present invention includes the B-stage coating of the present invention. The B-stage coating laminated film of the present invention has the B-stage coating of the present invention on at least one side of a film substrate. The B-stage coating laminated film of the present invention usually has the B-stage coating of the present invention on one side of a film substrate, and the B-stage coating forms a surface.

[0113] The B-stage coating film laminated film of the present invention can be produced by forming the B-stage coating film of the present invention on at least one surface of the above-mentioned film substrate by any method using the above-mentioned B-stage coating film forming paint (a paint containing the above-mentioned component (A) active energy ray curable resin and the above-mentioned component (B) photopolymerization initiator). The B-stage coating film laminated film of the present invention can be produced preferably by forming the B-stage coating film of the present invention on at least one surface of the above-mentioned film substrate by the B-stage coating film production method of the present invention using the above-mentioned B-stage coating film forming paint.

[0114] The method for producing a B-stage coating film of the present invention has been described in the section "1. Method for producing a B-stage coating film". The coating material for forming the B-stage coating film (a coating material containing the component (A) active energy ray curable resin and the component (B) photopolymerization initiator) has been described in the section "2. B-stage coating film".

[0115] Film Substrate The above-mentioned film substrate is a film that serves as a substrate for forming the B-stage coating film of the present invention on at least one surface thereof.

[0116] The film substrate is not particularly limited, and any film can be used as the film substrate. Examples of the film include polyester-based resins such as aromatic polyester and aliphatic polyester; acrylic resins; polycarbonate resins; poly(meth)acrylimide resins; polyolefin-based resins such as polyethylene, polypropylene, and poly4-methylpentene-1; cellulose-based resins such as cellophane, triacetyl cellulose, diacetyl cellulose, and acetyl cellulose butyrate; styrene-based resins such as polystyrene, acrylonitrile-butadiene-styrene copolymer resin (ABS resin), styrene-ethylene-butadiene-styrene copolymer, styrene-ethylene-propylene-styrene copolymer, and styrene-ethylene-ethylene-propylene-styrene copolymer; polyvinyl chloride resins; polyvinylidene chloride resins; fluorine-containing resins such as polyvinylidene fluoride; and other resin films such as polyvinyl alcohol, ethylene vinyl alcohol, polyether ether ketone, nylon, polyamide, polyimide, polyurethane, polyetherimide, polysulfone, and polyethersulfone. These films include unstretched films, uniaxially stretched films, and biaxially stretched films. They also include laminated films in which one or more of these films are laminated in two or more layers. Furthermore, these films may be transparent or opaque, may have a concealing property, may be colored, or may have an inherent color.

[0117] When the film substrate is used as one of the constituent materials of a molded product When the above-mentioned film substrate is used as one of the constituent materials of the molded body of the present invention (described later in the section "4. Molded body"), from the viewpoint of improving the adhesion between the above-mentioned film substrate and the B-stage coating film of the present invention, the coating film forming surface of the above-mentioned film substrate may be subjected to an adhesion-improving treatment such as a corona discharge treatment, a plasma treatment, or the formation of an anchor coat.

[0118] When the film substrate is used as one of the constituent materials of the molded body of the present invention, the thickness of the film substrate is appropriately determined in consideration of the use of the molded body. When the film substrate is used as one of the constituent materials of the molded body of the present invention, the thickness of the film substrate may be usually 20 μm or more, preferably 50 μm or more, from the viewpoint of handleability. The thickness of the film substrate may be usually 100 μm or more, preferably 150 μm or more, from the viewpoint of the strength of the molded body. On the other hand, the thickness of the film substrate may be usually 2000 μm or less, preferably 800 μm or less, more preferably 600 μm or less, from the viewpoint of weight reduction of the molded body.

[0119] When the film substrate is used as one of the constituent materials of the molded article of the present invention, it is preferable to use a film substrate having high transparency and no color. This allows the B-stage coating laminated film of the present invention to be suitably used as an article requiring high transparency and colorlessness, for example, a vehicle member such as a vehicle instrument panel. Examples of such films include transparent resin films such as cellulose ester resins such as triacetyl cellulose; polyester resins such as polyethylene terephthalate; cyclic hydrocarbon resins such as ethylene norbornene copolymers; acrylic resins such as polymethyl methacrylate, polyethyl methacrylate, and vinylcyclohexane-methyl (meth)acrylate copolymers; aromatic polycarbonate resins; polyolefin resins such as polypropylene and poly4-methylpentene-1; polyamide resins; polyarylate resins; polymer-type urethane acrylate resins; and polyimide resins. These films include unstretched films, uniaxially stretched films, and biaxially stretched films. These films also include laminated films in which one or more of these are laminated in two or more layers.

[0120] When the B-stage coating film laminated film of the present invention is used for an article that requires high transparency and colorlessness, the total light transmittance of the B-stage coating film laminated film of the present invention may be usually 80% or more, preferably 85% or more, more preferably 88% or more, and even more preferably 90% or more after the B-stage coating film is completely cured (made into a C-stage). The higher the total light transmittance, the better. The total light transmittance here is a value measured according to JIS K7361-1:1997. As a turbidity meter, for example, a turbidity meter "NDH2000" (product name) manufactured by Nippon Denshoku Industries Co., Ltd. can be used.

[0121] When the B-stage coating film laminated film of the present invention is used for an article that requires high transparency and colorlessness, and when clear transparency is desired, the haze of the B-stage coating film laminated film of the present invention may be usually 3% or less, preferably 2% or less, more preferably 1% or less after the B-stage coating film is completely cured (C-staged). From the viewpoint of obtaining clear transparency, a lower haze is preferable.

[0122] When the B-stage coating film laminate film of the present invention is used for an article requiring high transparency and colorlessness, and anti-glare property is also desired, the haze of the B-stage coating film laminate film of the present invention after the B-stage coating film is completely cured (reduced to C-stage) may be usually 3 to 30%, preferably 5 to 25%, and more preferably 7 to 20%, depending on the desired level of anti-glare property.

[0123] When the B-stage coating laminate film of the present invention is used for an article requiring high transparency and colorlessness, the yellowness index of the B-stage coating laminate film of the present invention may be usually 5 or less, preferably 3 or less, more preferably 2 to -2, and even more preferably 1 to -1. Here, the yellowness index is a value measured according to JIS K7105:1981. As a colorimeter, for example, a colorimeter "SolidSpec-3700" (product name) manufactured by Shimadzu Corporation can be used.

[0124] The transparent resin film may preferably be a transparent resin film of an acrylic resin. Examples of the acrylic resin include a (meth)acrylic acid ester (co)polymer, a copolymer mainly containing a structural unit derived from a (meth)acrylic acid ester (usually 50 mol% or more, preferably 65 mol% or more, more preferably 70 mol% or more), and modified products thereof. Note that (meth)acrylic means acrylic or methacrylic. Also, a (co)polymer means a polymer or copolymer.

[0125] Examples of the (meth)acrylic acid ester (co)polymer include polymethyl(meth)acrylate, polyethyl(meth)acrylate, polypropyl(meth)acrylate, polybutyl(meth)acrylate, methyl(meth)acrylate-butyl(meth)acrylate copolymer, and ethyl(meth)acrylate-butyl(meth)acrylate copolymer.

[0126] Examples of copolymers mainly containing structural units derived from the above-mentioned (meth)acrylic acid esters include ethylene-methyl (meth)acrylate copolymers, styrene-methyl (meth)acrylate copolymers, vinylcyclohexane-methyl (meth)acrylate copolymers, maleic anhydride-methyl (meth)acrylate copolymers, and N-substituted maleimide-methyl (meth)acrylate copolymers.

[0127] Examples of the modified polymers include a polymer having a lactone ring structure introduced by an intramolecular cyclization reaction; a polymer having glutaric anhydride introduced by an intramolecular cyclization reaction; and a polymer having an imide structure introduced by reacting with an imidizing agent (e.g., methylamine, cyclohexylamine, ammonia, etc.).

[0128] The transparent resin film of the acrylic resin may be one or a mixture of two or more of these films, and may also be a laminate film in which two or more layers of one or more of these films are laminated.

[0129] More preferred examples of the transparent resin film include a transparent film of a copolymer of a (meth)acrylic acid ester and a polymerizable monomer having an imide structure, such as an N-substituted maleimide-methyl (meth)acrylate copolymer; and a polymer into which an imide structure has been introduced by reacting an acrylic resin with an imidizing agent (hereinafter, these may be collectively referred to as "poly(meth)acrylimide-based resin"); and a transparent multilayer film containing one or more layers formed using the poly(meth)acrylimide-based resin. By using such a transparent film or transparent multilayer film as the film substrate of the B-stage coating film laminate film of the present invention, a molded article formed using the B-stage coating film laminate film of the present invention can have excellent surface hardness, scratch resistance, transparency, surface smoothness, appearance, rigidity, heat resistance, and heat-resistant dimensional stability.

[0130] The poly(meth)acrylimide-based resin can also be defined as a thermoplastic resin having both an acrylic structure and an imide structure. The poly(meth)acrylimide-based resin has the characteristics of high transparency, high surface hardness, and high rigidity of acrylic resins because of the acrylic structure. In addition, the poly(meth)acrylimide-based resin has the characteristics of excellent heat resistance and dimensional stability of polyimide because of the imide structure. Furthermore, the poly(meth)acrylimide-based resin has been improved from the drawback of polyimide being colored from pale yellow to reddish brown.

[0131] The glass transition temperature of the poly(meth)acrylimide resin may be, from the viewpoint of heat resistance, usually 110° C. or higher, preferably 115° C. or higher, more preferably 120° C. or higher, even more preferably 130° C. or higher, and even more preferably 140° C. or higher. On the other hand, the glass transition temperature of the poly(meth)acrylimide resin may be, from the viewpoint of three-dimensional moldability, usually 170° C. or lower, preferably 165° C. or lower, more preferably 160° C. or lower, and even more preferably 155° C. or lower. Here, the glass transition temperature is the midpoint glass transition temperature calculated from the curve of the final heating process measured according to JIS K7121-1987, in a program in which the temperature is held at 250° C. for 3 minutes, cooled to 20° C. at 10° C. / min, held at 20° C. for 3 minutes, and heated to 250° C. at 10° C. / min. As the differential scanning calorimeter, for example, Diamond DSC from PerkinElmer Japan Co., Ltd. can be used.

[0132] The yellowness index of the poly(meth)acrylimide resin may be usually 5 or less, preferably 3 or less, more preferably 2 to -2, and even more preferably 1 to -1. By using a poly(meth)acrylimide resin having a yellowness index of 5 or less, it is possible to obtain a B-stage coating laminate film having a color tone suitable for vehicle members such as vehicle instrument panels, and a molded article using the same. Here, the yellowness index is a value measured according to JIS K7105:1981. As a colorimeter, for example, a colorimeter "SolidSpec-3700" (product name) manufactured by Shimadzu Corporation can be used.

[0133] The melt mass flow rate of the poly(meth)acrylamide resin (measured according to ISO1133 under conditions of 260°C and 98.07N) may be preferably 0.1 to 20 g / 10 min, more preferably 0.5 to 10 g / 10 min, from the viewpoints of the extrusion load during film formation and the stability of the molten film.

[0134] The poly(meth)acrylamide resin may further contain, if desired, additives such as thermoplastic resins other than poly(meth)acrylamide resins, pigments, inorganic fillers, organic fillers, resin fillers, lubricants, antioxidants, weathering stabilizers, heat stabilizers, release agents, antistatic agents, and surfactants, within the limits not contrary to the object of the present invention. The amount of these optional components is usually 10 parts by mass or less, or about 0.01 to 10 parts by mass, based on 100 parts by mass of the poly(meth)acrylamide resin.

[0135] The transparent resin film may be preferably a transparent multilayer film in which an acrylic resin layer (α) and an aromatic polycarbonate resin layer (β) are directly laminated in this order. The transparent resin film may more preferably be a transparent multilayer film in which a first acrylic resin layer (α1), an aromatic polycarbonate resin layer (β), and a second acrylic resin layer (α2) are directly laminated in this order.

[0136] Acrylic resins have excellent surface hardness but tend to have insufficient cutting workability, whereas aromatic polycarbonate resins have excellent cutting workability but tend to have insufficient surface hardness. Therefore, by using a transparent multilayer film with the above layer structure, the weaknesses of both resins are compensated for, and after the B-stage coating film is completely cured (C-stage), a B-stage coating film laminate film with excellent surface hardness and cutting workability can be easily obtained.

[0137] Hereinafter, a transparent multilayer film having a first acrylic resin layer (α1), an aromatic polycarbonate resin layer (β), and a second acrylic resin layer (α2) directly laminated in this order will be described assuming that a B-stage coating film is formed on the α1 layer side.

[0138] The thickness of the α1 layer is not particularly limited, but from the viewpoint of the surface hardness after the B-stage coating film is completely cured (C-stage), it may be usually 20 μm or more, preferably 40 μm or more, more preferably 50 μm or more, and even more preferably 80 μm or more.

[0139] The thickness of the α2 layer is not particularly limited, but from the viewpoint of curl resistance, it is preferably the same thickness as that of the α1 layer.

[0140] Here, "the same layer thickness" should not be interpreted as the same layer thickness in the strict physicochemical sense. It should be interpreted as the same layer thickness within the range of fluctuation of the process and quality control usually performed in the industry. This is because the curl resistance of the multilayer film can be maintained well if the layer thickness is the same within the range of fluctuation of the process and quality control usually performed in the industry. In the case of non-oriented multilayer films produced by the T-die coextrusion method, the process and quality control are usually performed within a range of about -5 to +5 μm, so for example, a layer thickness of 65 μm and 75 μm should be interpreted as the same.

[0141] The thickness of the β layer is not particularly limited, but from the viewpoint of machinability, it may be usually 20 μm or more, and preferably 70 μm or more.

[0142] The acrylic resin used in the α1 layer and the α2 layer has been described above.

[0143] The acrylic resin used in the α1 layer and the acrylic resin used in the α2 layer may have different resin properties, such as different types, melt mass flow rates, and glass transition temperatures. From the viewpoint of the curl resistance of the transparent multilayer film, it is preferable to use resins with the same resin properties. For example, using the same lot of the same grade is one of the preferred embodiments.

[0144] The aromatic polycarbonate resin used in the β layer may be one or a mixture of two or more of aromatic polycarbonate resins such as polymers obtained by interfacial polymerization of aromatic dihydroxy compounds such as bisphenol A, dimethyl bisphenol A, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, and phosgene; or polymers obtained by transesterification of aromatic dihydroxy compounds such as bisphenol A, dimethyl bisphenol A, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, and a carbonate diester such as diphenyl carbonate.

[0145] A preferred optional component that may be contained in the aromatic polycarbonate resin is a core-shell rubber. When the total of the aromatic polycarbonate resin and the core-shell rubber is 100 parts by mass, the core-shell rubber is used in an amount of 0 to 30 parts by mass (100 to 70 parts by mass of the aromatic polycarbonate resin), preferably 0 to 10 parts by mass (100 to 90 parts by mass of the aromatic polycarbonate resin), thereby making it possible to further improve the machinability and impact resistance.

[0146] Examples of the core-shell rubber include methacrylate ester-styrene / butadiene rubber graft copolymer, acrylonitrile-styrene / butadiene rubber graft copolymer, acrylonitrile-styrene / ethylene-propylene rubber graft copolymer, acrylonitrile-styrene / acrylic ester graft copolymer, methacrylate ester / acrylic ester rubber graft copolymer, methacrylate ester-styrene / acrylic ester rubber graft copolymer, and methacrylate ester-acrylonitrile / acrylic ester rubber graft copolymer. As the core-shell rubber, one or a mixture of two or more of these may be used.

[0147] Furthermore, the aromatic polycarbonate resin may further contain, as desired, additives such as thermoplastic resins other than the aromatic polycarbonate resin and the core-shell rubber, pigments, inorganic fillers, organic fillers, resin fillers, lubricants, antioxidants, weather resistance stabilizers, heat stabilizers, release agents, antistatic agents, and surfactants, within the limits not contrary to the object of the present invention. The amount of these optional components is usually 10 parts by mass or less, or about 0.01 to 10 parts by mass, when the total of the aromatic polycarbonate resin and the core-shell rubber is 100 parts by mass.

[0148] The manufacturing method of the transparent resin film is not particularly limited. When the transparent resin film is a transparent multilayer film in which a first poly(meth)acrylamide resin layer (α1), an aromatic polycarbonate resin layer (β), and a second poly(meth)acrylamide resin layer (α2) are directly laminated in this order, a preferred manufacturing method can be the method described in JP 2015-083370 A. In addition, when forming the B-stage coating film, one or both sides of the transparent resin film may be subjected to a corona discharge treatment, a plasma treatment, and an easy-adhesion treatment such as anchor coat formation in advance in order to increase the adhesive strength with the B-stage coating film.

[0149] The total light transmittance of the transparent resin film may be usually 85% or more, preferably 88% or more, more preferably 90% or more. The higher the total light transmittance, the better. By using a transparent resin film with a total light transmittance of 85% or more, it is possible to obtain an article requiring high transparency, for example, a B-stage coating film laminate film suitable as a vehicle member such as a vehicle instrument panel, and a molded article using the same. Here, the total light transmittance is a value measured according to JIS K7361-1:1997. As the turbidity meter, for example, a turbidity meter "NDH2000" (product name) manufactured by Nippon Denshoku Industries Co., Ltd. can be used.

[0150] The yellowness index of the transparent resin film may be usually 5 or less, preferably 3 or less, more preferably 2 to -2, and even more preferably 1 to -1. By using a transparent resin film having a yellowness index of 5 or less, it is possible to obtain an article requiring high colorlessness, for example, a B-stage coating film laminate film suitable for vehicle members such as an instrument panel of a vehicle, and a molded article using the same. Here, the yellowness index is a value measured according to JIS K7105:1981. As a colorimeter, for example, a colorimeter "SolidSpec-3700" (product name) manufactured by Shimadzu Corporation can be used.

[0151] The retardation of the transparent resin film may be usually 75 nm or less, preferably 50 nm, more preferably 40 nm or less, even more preferably 30 nm or less, even more preferably 20 nm or less, and most preferably 15 nm or less. The lower the retardation, the better. By using a transparent resin film having a retardation of 75 nm or less, it is possible to obtain an article that requires clear transparency, for example, a B-stage coating film laminate film suitable for vehicle components such as vehicle instrument panels, and a molded article using the same. Here, the retardation is a value measured by a parallel Nicol rotation method. As a measuring device, for example, a phase difference measuring device "KOBRA-WR" (product name) by parallel Nicol rotation method of Oji Scientific Instruments Co., Ltd. can be used.

[0152] When transferring the formed B-stage coating film to another substrate When the B-stage coating film of the present invention formed on the surface of the above-mentioned film substrate is transferred to another substrate (e.g., a film, a sheet, a plate, and a substrate of any shape) for use (i.e., the film substrate does not constitute a molded article), the coating film-forming surface of the above-mentioned film substrate may be treated to facilitate peeling.

[0153] When the B-stage coating film of the present invention formed on the surface of the film substrate is transferred to another substrate, the thickness of the film substrate is not particularly limited.When the B-stage coating film of the present invention formed on the surface of the film substrate is transferred to another substrate, the thickness of the film substrate may be generally 20 μm or more, preferably 30 μm or more, from the viewpoint of handling.On the other hand, in this case, the thickness of the film substrate may be generally 100 μm or less, preferably 75 μm or less, from the viewpoint of economic efficiency.

[0154] When the B-stage coating film of the present invention formed on the surface of the above-mentioned film substrate is transferred to another substrate for use, the above-mentioned film substrate is preferably, for example, a biaxially oriented film of a polyester resin such as polyethylene terephthalate, or a biaxially oriented film of a polypropylene resin.

[0155] 4. Molded body The molded article of the present invention has a coating film (C stage) obtained by completely curing the B-stage coating film of the present invention. In the molded article of the present invention, the coating film (C stage) obtained by completely curing the B-stage coating film of the present invention usually constitutes a part or the whole of the surface of the molded article. The molded article of the present invention can be produced by imparting a desired shape to the B-stage coating film of the present invention (and the substrate) and then completely curing the B-stage coating film (C stage). Examples of such molded articles include films, sheets, and plates (molded articles that maintain a flat shape) having a coating film (C stage) obtained by completely curing the B-stage coating film of the present invention; molded articles obtained by imparting a desired shape by thermoforming such as vacuum molding, pressure molding, and press molding using a film or sheet having the B-stage coating film of the present invention, and then completely curing the B-stage coating film (C stage); and composite molded articles obtained by inserting a film or sheet having the B-stage coating film of the present invention into a mold as a skin material, injecting any thermoplastic resin as a core material, and then completely curing the B-stage coating film (C stage).

[0156] An example of a method for producing a molded article of the present invention by using the B-stage coating laminate film of the present invention (the coating film is B-stage) and applying a three-dimensional molding method such as vacuum molding or vacuum pressure molding to give a three-dimensional shape, and then completely curing the B-stage coating film (to C-stage) will be described.

[0157] FIG. 4 is a conceptual diagram showing an example of a vacuum molding device. First, as shown in FIG. 4(a), the B-stage coating film laminated film 7 is heated and softened using a heating device 8 such as an infrared heater. Next, the B-stage coating film laminated film 7 is removed from the heating device 8, and the B-stage coating film laminated film 7 is quickly placed over the mold 9 so that the surface opposite to the B-stage coating film side of the B-stage coating film laminated film 7 faces the mold 9 (FIG. 4(b)). At this time, the mold 9 may be preheated. Next, the space 10 between the B-stage coating film laminated film 7 and the mold 9 is depressurized, the B-stage coating film laminated film 7 is brought into close contact with the mold 9, and the shape of the mold 9 is transferred to the B-stage coating film laminated film 7 to obtain a molded body 11 (the coating film is B-stage) (FIG. 4(c)). Before releasing the molded body 11 from the mold 9, the mold 9 may be cooled. Next, the B-stage coating film of the molded body 11 is completely cured (to C-stage) using any active energy ray irradiation device, thereby producing the molded body of the present invention.

[0158] The pressure in the space 10 may be preferably 10 KPa or less, more preferably 1 KPa or less, from the viewpoint of sufficient adhesion without leaving any air between the B-stage coating laminated film 7 and the mold 9. The adhesion force increases as the pressure in the space 10 decreases, but in consideration of the fact that reducing the pressure increases costs exponentially and the mechanical strength of the B-stage coating laminated film 7, the lower limit of the pressure in the space 10 is practically 10 -5 It may be about KPa.

[0159] The amount of irradiation of the active energy rays is appropriately selected and determined from the viewpoint of a necessary and sufficient amount of irradiation for completely curing the B-stage coating film (to the C-stage). The amount of irradiation of the active energy rays is usually 10 to 10,000 mJ / cm 2Approximately, preferably 200 to 2000 mJ / cm 2 , more preferably 300 to 700 mJ / cm 2 It may be.

[0160] In one embodiment, the molded article of the present invention may have a coating film (C stage) obtained by completely curing the B-stage coating film of the present invention and an arbitrary substrate. The molded article of this embodiment can be produced, for example, by using the substrate instead of the mold 9, adhering and integrating the B-stage coating film laminated film 7 with the substrate, and then completely curing the B-stage coating film (to the C stage). Examples of the substrate include substrates made of wood-based materials such as wood, plywood, laminated lumber, particle board, and hardboard; substrates made of resin-based materials such as polystyrene, acrylonitrile-butadiene-styrene copolymer (ABS resin), polycarbonate, polyester, polyvinyl chloride, and polyolefin; substrates made of metal-based materials such as iron and aluminum; and substrates made of mineral-based materials such as gypsum and calcium silicate.

[0161] Since the molded article of the present invention has the preferred properties as described above, it can be suitably used as an article (including a member of an article). Examples of the above-mentioned article include image display devices such as liquid crystal displays, plasma displays, and electroluminescence displays, and their display panels, transparent conductive substrates, and housings; televisions, personal computers, tablet-type information devices, smartphones, and their housings and display panels; refrigerators, washing machines, cupboards, wardrobes, and panels constituting these devices; windows and doors of buildings; vehicles, vehicle windows, windshields, roof windows, and instrument panels; head-up displays, electronic signs, and their protective plates; show windows; solar cells, and their housings and front panels, and other members. EXAMPLES

[0162] The present invention will be described below with reference to examples, but the present invention is not limited to these.

[0163] Measurement and evaluation methods for physical properties (i) Three-dimensional formability 1 The laminated film (coating film is in B stage) was preheated using an infrared heater, and then the laminated film was spread and layered on a mold (see FIG. 5) preheated to 130° C., with the surface of the laminated film opposite the coating surface facing the mold. FIG. 5(a) is a front view of the mold, where the height (h) is 10 mm and the radius of curvature (R) of the curved portion around the mold is 16.25 mm. FIG. 5(b) is a plan view of the mold, where the diameter (φ) of the outer periphery is 90 mm. As described above, the laminated film was left to stand for 30 seconds in the spread-out layered state on the mold, and then the space between the laminated film and the mold was pressurized with a pressure of 1.0×10 -3 The pressure was reduced to 100 MPa, and the shape of the mold was transferred to the laminated film. is B The B-stage coating film of the molded product was irradiated with ultraviolet light of a high-pressure mercury lamp type with an integrated light quantity of 600 mJ / cm2. 2 The laminated film was irradiated under the conditions of (a) to completely cure (to C stage) to obtain a molded product (coating film was C stage). The appearance of the molded product (coating film was C stage) was visually observed by a person with corrected vision of 1.0 with the naked eye or using a loupe (10x) and evaluated according to the following criteria. In addition, in the case where the laminated film had a protective film, the protective film was peeled off after the B stage coating film was completely cured by ultraviolet irradiation, and the product was subjected to visual observation. A: Even with the use of a magnifying glass, no cracks, breaks, or defects in appearance were observed. B: No cracks or breaks were found even with a magnifying glass. However, when viewed up close through a light, there were some areas that were slightly cloudy. C: When using a magnifying glass, slight cracks and breaks were found in the curved areas around the periphery. D: Cracks and breaks were visible to the naked eye.

[0164] (ii) Three-dimensional formability 2 The molded bodies were prepared, observed and evaluated in the same manner as in the above test (i) Three-dimensional moldability 1, except that a mold with a height (h) of 13.5 mm, a radius of curvature (R) of the surrounding curved part of 13.5 mm, and an outer diameter (φ) of 90 mm was used.

[0165] (iii) Tensile elongation (tensile elongation of laminated film with B-stage coating) In accordance with JIS K7127:1999, a type 2 test piece (width 15 mm, total length 150 mm) was taken from a laminated film having a B-stage coating so that the width direction of the laminated film coincided with the tensile direction, and the tensile elongation was measured under the conditions of a gauge length of 50 mm, an initial distance between chucks of 100 mm, and a test speed of 10 mm / min. During the tensile test, the test piece was visually observed, and the elongation at the moment when a crack occurred in the coating of the test piece was taken as the tensile elongation of the laminated film. Note that, technically, the value of the tensile elongation of the test (iii) is considered to correspond to the tensile elongation of the B-stage coating of the laminated film. In addition, when the laminated film had a protective film, the protective film was peeled off after the test piece was taken and used for the test.

[0166] (iv) Environmental Test 1 The molded article (coating film was in C stage) obtained in the above test (ii) was treated for 4 hours in a Geer oven at a temperature of 90°C, and then the appearance of the molded article (coating film was in C stage) was visually observed by a person with corrected vision of 1.0 with the naked eye or using a loupe (10x) and evaluated according to the following criteria. In addition, in the case where the laminated film had a protective film, the protective film was peeled off after the Geer oven treatment and the product was subjected to visual observation. A: Even with the use of a magnifying glass, no cracks, breaks, or defects in appearance were observed. B: No cracks or breaks were found even with a magnifying glass. However, when viewed up close through a light, there were some areas that were slightly cloudy. C: When using a magnifying glass, slight cracks and breaks were found in the curved areas around the periphery. D: Cracks and breaks were visible to the naked eye.

[0167] (v) Environmental Test 2 Except for changing the temperature of the gear oven to 130°C, the molded body was treated, observed, and evaluated in the same manner as in the above test (iv) Environmental Test 1.

[0168] For the following tests of (vi) pencil hardness, (vii) total light transmittance, (viii) haze, (ix) chemical resistance, (x) cross-cut adhesion test, (xi) cross-cut adhesion test after moist heat treatment, and (xii) scratch resistance, the B-stage coating film of the laminated film having the B-stage coating film was exposed to ultraviolet light irradiation using a high-pressure mercury lamp type ultraviolet ray irradiation device with an accumulated light amount of 600 mJ / cm. 2 The samples were used after being completely cured (C stage) under the above conditions. For samples having a protective film, the protective film was peeled off before the test.

[0169] (vi) Pencil hardness The pencil hardness of the coating film surface of the sample was measured using a "Uni" (trade name) pencil manufactured by Mitsubishi Pencil Co., Ltd. under conditions of a test length of 25 mm and a load of 750 g in accordance with JIS K 5600-5-4:1999. The occurrence of scratches was judged by visually observing the surface of the sample under a fluorescent lamp at a position 50 cm away from the fluorescent lamp.

[0170] (vii) Total light transmittance The total light transmittance of the above sample was measured using a turbidity meter "NDH2000" (product name) manufactured by Nippon Denshoku Industries Co., Ltd. in accordance with JIS K7361-1:1997.

[0171] (viii) Haze The haze of the above sample was measured using a turbidity meter "NDH2000" (product name) manufactured by Nippon Denshoku Industries Co., Ltd. in accordance with JIS K7136:2000.

[0172] (ix) Chemical resistance A test solution was prepared by mixing 20 ml of Johnson & Johnson's sunscreen Neutrogena Ultra Sheer Dry Touch Sunblock (trade name) with 10 drops of Pilot Ink Red (trade name) red ink from Pilot Corporation. A test piece measuring 100 mm x 100 mm was taken from the above sample, and a paper wiper (Kimwipe (trade name) from Nippon Paper Crecia Co., Ltd.) cut to a size of 30 mm x 40 mm was spread on the coating surface of the test piece, and 10 drops of the test solution were evenly dropped onto the paper wiper using a dropper. After dropping, air bubbles were removed between the paper wiper and the test piece using tweezers, and the paper wiper and the test piece were brought into close contact with each other, and then the test piece was stored in an environment with a temperature of 23°C and a relative humidity of 50%. The storage was continued for 72 hours, with the operation of dropping 10 drops of the test solution, removing air bubbles, and bringing the test piece into close contact being repeated every 24 hours of storage. After a predetermined time had elapsed, the paper wiper containing the test liquid on the test piece was removed, the test piece was wiped with a paper wiper soaked in water, and then wiped dry with a dry paper wiper to remove the test liquid adhering to the surface of the test piece.Then, the test piece was visually observed by a person with corrected vision of 1.0 with the naked eye or using a loupe (10x magnification), and evaluated according to the following criteria. A: No cracks were observed even with a magnifying glass. No difference in color was observed between the areas of the coating surface of the laminated film that had come into contact with the test solution and those that had not. B: No cracks were observed even with a magnifying glass. However, there was a difference in color between the areas of the coating surface of the laminated film that had come into contact with the test liquid and those that had not. (The areas that had come into contact were reddish compared to the non-contact areas.) C: No cracks were visible to the naked eye, but were visible using a magnifying glass. D: Cracks were visible to the naked eye.

[0173] (x) Cross-cut test (coating adhesion) According to JIS K5600-5-6:1999, 100 grids (1 grid = 1mm x 1mm) were cut into the coating side of the sample, and then adhesion test tape was applied to the grids, rubbed with fingers, and then peeled off. The evaluation criteria were according to Table 1 of the above JIS standard. Category 0: The edges of the cut were completely smooth and there was no delamination on any of the grid cells. Category 1: Small separations of the coating at the intersections of cuts. The area affected at the cross cuts did not appreciably exceed 5%. Category 2: The coating had flaked along the edges of the cuts and / or at the intersections. The area affected at the cross cuts was clearly greater than 5% but not greater than 15%. Category 3: The coating had suffered partial or complete major flaking along the edges of the cuts and / or partial or complete flaking in various areas of the mesh. The area affected in the cross cuts was clearly greater than 15% but not more than 35%. Category 4: The coating had suffered partial or complete major flaking along the edges of the cuts and / or partial or complete flaking in a few sections. The area affected in the cross-cuts was clearly greater than 35% but not greater than 65%. Class 5: This classification was used when the degree of peeling exceeded that of Class 4.

[0174] (xi) Cross-cut test after moist heat treatment (moist heat test) The above sample was subjected to a wet heat treatment under conditions of a temperature of 85° C. and a relative humidity of 85% for 72 hours, and then tested in the same manner as in the above test (x) cross-cut test to evaluate adhesion.

[0175] (xii) Scratch resistance (steel wool resistance) A test piece measuring 150mm long and 50mm wide, with the machine direction of the laminated film aligned with the length of the test piece, was placed in a Gakushin type testing machine (friction testing machine type 2) of JIS L0849:2013 so that the coating film was on the surface. Next, after attaching #0000 steel wool to the friction terminal of the Gakushin type testing machine, a 250g load was placed on the test piece's coating film surface, and the friction terminal was rubbed back and forth five times at a moving speed of 300mm / min and a moving distance of 30mm, and the rubbed area was visually observed. If no scratches were found, the test piece was rubbed back and forth five more times and the rubbed area was visually observed, and the results were evaluated according to the following criteria. A: No scratches were found even after 15 round trips. B: No scratches were observed after 10 round trips, but scratches were observed after 15 round trips. C: No scratches were observed after five round trips, but scratches were observed after ten round trips. D: After five round trips, the wound could be seen.

[0176] Raw materials used (A) Active energy ray curable resin (A1) Urethane (meth)acrylate (A1-1) EBECRYL284 (product name), a multifunctional urethane (meth)acrylate from Daicel-Allnex Corporation. Solid content 100% by mass, functional group number 2, number average molecular weight 1000, mass average molecular weight 2900, Z-average molecular weight 4700. (A1-2) EBECRYL4101 (product name), a multifunctional urethane (meth)acrylate from Daicel-Allnex Corporation. Solid content 100% by mass, functional group number 3, number average molecular weight 1100, mass average molecular weight 2800, Z-average molecular weight 4900. (A1-3) "Art Resin UN-952" (product name) is a diluted solution of multifunctional urethane (meth)acrylate from Negami Chemical Industrial Co., Ltd. Solid content 60% by mass, number of functional groups 10, number average molecular weight 2500, mass average molecular weight 9100, Z average molecular weight 23000. (A1-4) "Art Resin UN-954" (product name) is a diluted solution of multifunctional urethane (meth)acrylate from Negami Chemical Industrial Co., Ltd. Solid content 60% by mass, number of functional groups 6, number average molecular weight 2000, mass average molecular weight 4800, Z average molecular weight 9600.

[0177] (A2) (a1) Copolymer of multifunctional (meth)acrylate and (a2) multifunctional thiol (A2-1) "SIRIUS-501" (product name) from Osaka Organic Chemical Industry Co., Ltd. A dilute solution of a copolymer having a so-called dendrimer structure of dipentaerythritol hexaacrylate and tetrafunctional thiol. Solid content 50% by mass, sulfur content 2.2% by mass, mass average molecular weight 12,000, number average molecular weight 940, Z-average molecular weight 73,000.

[0178] (B) Photopolymerization initiator (B-1) IGM Resins' acetophenone-based photopolymerization initiator (2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one) "Omnirad127" (trade name). (B-2) IGM Resins' acetophenone-based photopolymerization initiator (1-hydroxycyclohexyl-phenyl ketone) "Omnirad 184" (trade name).

[0179] (C) Fine particles (C-1) Propylene glycol monomethyl ether dispersion of silica fine particles "PGM-AC-2140Y" (product name) from Nissan Chemical Co., Ltd. Solid content 42% by mass, average particle size 15 nm. (C-2) Antiviral agent (ethanol suspension of cuprous iodide microparticles) from NBC Meshtec Co., Ltd., with an average particle size of cuprous iodide microparticles (the particle size at which the cumulative total from the smallest particles in a particle size distribution curve measured by a laser diffraction / scattering method is 50% by mass) of 120 nm and a solid content of 11% by mass.

[0180] (D) Water repellent (D-1) "KY-1203" (product name) is a diluted solution of an acryloyl group-containing fluoropolyether water repellent from Shin-Etsu Chemical Co., Ltd. Solid content: 20% by mass. (D-2) Fluoroalkyl water repellent containing an acryloyl group (2-(perfluorobutyl)ethyl acrylate) "CHEMINOXFAAC-4" (product name) from Unimatec Co., Ltd. Solid content: 100% by mass.

[0181] (E) Other ingredients (E-1) Big Chemie Japan Co., Ltd.'s amine-based dispersant "DISPERBY K-145" (product name). Phosphate salt of high molecular weight copolymer with polyamine structure. Amine value 71 mg KOH / g. Solid content 100% by mass.

[0182] (H) B-stage coating film forming paint (H-1) 50 parts by mass of the above component (A1-1), 100 parts by mass of the above component (A2-1) (50 parts by mass in terms of solid content), 5 parts by mass of the above component (B-1), 555 parts by mass of the above component (C-1) (233 parts by mass in terms of solid content), 1.25 parts by mass of the above component (D-1) (0.25 parts by mass in terms of solid content), and 233 parts by mass of methyl isobutyl ketone (referred to as "MIBK" in the table) were mixed and stirred to obtain a coating material for forming a B-stage coating film. In the table, all values ​​are given in terms of solid content, except for the solvent.

[0183] (H-2~H-11) A paint was obtained in the same manner as in (H-1) above, except that the formulation was changed as shown in any one of Tables 1 to 3. In the table, all values ​​shown are calculated as solid contents, except for the solvent.

[0184] (P) Transparent resin film (P-1) A device equipped with a two-kind, three-layer multi-manifold type coextrusion T-die and a take-up machine having a mechanism for pressing the molten film between the first mirror roll (the roll that holds the molten film and sends it to the next transfer roll) and the second mirror roll was used, and Evonik's poly(meth)acrylamide "PLEXIMID TT50" (product name) was continuously coextruded from the coextrusion T-die as both outer layers (α1 layer and α2 layer) of the two-kind, three-layer multilayer resin film, and Sumika Styron Polycarbonate Co., Ltd.'s aromatic polycarbonate "Caliber 301-4" (product name) was continuously coextruded from the coextrusion T-die, and the α1 layer was fed and fed between the rotating first mirror roll and second mirror roll so that the α1 layer was on the first mirror roll side, and pressed to obtain a transparent resin film with a total thickness of 170 μm, a layer thickness of 50 μm for the α1 layer, a layer thickness of 70 μm for the β layer, and a layer thickness of 50 μm for the α2 layer. The conditions were as follows: T-die temperature 300° C., first mirror roll temperature 130° C., second mirror roll temperature 120° C., and take-off speed 9.5 m / min.

[0185] (Q) Protective Film (Q-1) Teijin Limited's aromatic polycarbonate resin film "Panlite Film PC-2151" (product name), thickness 125 μm. (Q-2) Using a film-forming device equipped with a single-layer T-die and a take-up machine having a mechanism for nipping the molten film extruded from the single-layer T-die with a first chill roll (mirror metal roll) and a nip roll (silicon rubber roll), a resin film having a thickness of 75 μm was obtained using copolymerized polyethylene terephthalate resin "PIFG5" (product name) from Bell Polyester Products Co., Ltd. under the conditions of a set temperature of the T-die of 250°C, a set temperature of the first chill roll of 50°C, and a take-up speed of 10.8 m / min. The surface of the resin film facing the first chill roll (high gloss surface) was used as the surface to be laminated with the coating film.

[0186] Example 1 (1) Both sides of the above (P-1) were subjected to a corona discharge treatment. The wettability index of both sides was 64 mN / m. (2) Next, the above (H-1) was applied onto the α1 layer side of the above (P-1) using a die-type coating device so that the thickness after complete curing (C stage) would be 18 μm, forming a wet coating film. (3) Next, the wet coating film was pre-dried by passing it through a drying furnace set at an internal temperature of 90°C at a line speed such that the time required for passing from the entrance to the exit was 2 minutes, thereby forming a dry coating film. (4) Next, using a laminating device whose conceptual diagram is shown in FIG. 1, the laminate 1 having the above-mentioned dry coating film on the surface of the α1 layer side of the above-mentioned (P-1) was placed on the rotating drum 3 so that the surface of the laminate 1 opposite to the dry coating film was on the rotating drum 3 side. At the same time, the protective film 2 of the above-mentioned (Q-1) was superimposed on the above-mentioned dry coating surface of the above-mentioned laminate 1 so that the surface (high gloss surface) of the above-mentioned protective film 2 of the above-mentioned (Q-1) on the first chill roll side was on the above-mentioned dry coating surface side, and was pressed by a pressing roll 4, and then released from the rotating drum 3 by a guide roll 6, to obtain a laminate 5 in which the above-mentioned protective film 2 of the above-mentioned (Q-1) was superimposed on the above-mentioned dry coating surface of the above-mentioned laminate 1 and temporarily attached. At this time, the temperature of the rotating drum 3 was set to room temperature (23° C.). (5) Next, an autoclave "YKP-500 type" (product name) manufactured by Kurihara Manufacturing Co., Ltd. was used, and the laminate having the above-mentioned (P-1), the above-mentioned dried coating film, and the above-mentioned (Q-1) in this order was placed in the autoclave, and then autoclaved under conditions of a temperature of 50°C, a pressure of 0.5 MPa, and a holding time of 10 minutes. (6) Subsequently, an aging treatment was performed at a temperature of 80° C. for 2 hours to form a B-stage coating film, thereby obtaining a laminated film having a B-stage coating film on the surface of the α1 layer side of the above (P-1). (7) The above tests (i) to (xii) were carried out. The results are shown in Table 1.

[0187] Examples 2-10 A laminated film having a B-stage coating film was obtained in the same manner as in Example 1, except that the coating material shown in Table 1 or 2 was used instead of the above (H-1) as the coating material for forming a B-stage coating film. The above tests (i) to (xii) were carried out. The results are shown in Table 1 or 2.

[0188] Example 11 A laminated film having a B-stage coating film was obtained in the same manner as in Example 1, except that the coating material for forming the B-stage coating film was replaced with the coating material (H-1) above instead of the coating material (H-11), and the protective film was replaced with the coating material (Q-2) above instead of the coating material (Q-1). The above tests (i) to (xii) were carried out. The results are shown in Table 2.

[0189] Example 12 A laminated film having a B-stage coating film was obtained in the same manner as in Example 1, except that the wet coating film was applied so that the thickness after complete curing (C-stage) would be 13 μm. The above tests (i) to (xii) were carried out. The results are shown in Table 3.

[0190] Example 13 A laminate film having a B-stage coating film was obtained in the same manner as in Example 1, except that the pre-drying conditions were changed to those shown in Table 1. The above tests (i) to (xii) were carried out. The results are shown in Table 3.

[0191] Examples 14-17 A laminate film having a B-stage coating film was obtained in the same manner as in Example 1, except that the autoclave treatment conditions were changed to those shown in Table 1. The above tests (i) to (xii) were carried out. The results are shown in Table 3.

[0192] Example 18 A laminated film having a B-stage coating was obtained in the same manner as in Example 1, except that the autoclave treatment was omitted. When the above test (i) was carried out, many defects in appearance due to foaming of the coating were observed in the obtained molded product. Therefore, tests (ii) to (xii) were omitted.

[0193] [Table 1]

[0194] [Table 2]

[0195] [Table 3]

[0196] The manufacturing method of the present invention allows the B-stage coating film to be manufactured industrially and stably. The preferred manufacturing method of the present invention allows the B-stage coating film with excellent three-dimensional moldability to be manufactured industrially and stably. The preferred B-stage coating film of the present invention has excellent three-dimensional moldability in the B stage, and after complete curing (in the C stage), has excellent heat resistance, surface hardness, transparency, chemical resistance, coating adhesion, coating adhesion after a wet heat test, and scratch resistance. Therefore, the B-stage coating film of the present invention can be suitably used to impart functions such as surface hardness, scratch resistance, and chemical resistance to the surface of a molded body having a three-dimensional shape / stereoscopic shape, such as the housing of a home appliance or information electronic device, and an instrument panel of an automobile.

[0197] Examples of B-stage coating embodiments of the present invention are summarized as follows. [1]. A B-stage coating film, (A) is formed using a coating material containing an active energy ray curable resin and (B) a photopolymerization initiator; The tensile elongation of the B-stage coating is 10% or more; The above B-stage coating. [2]. The B-stage coating film according to item [1], wherein the coating further contains (C) fine particles having an average particle diameter of 1 to 300 nm. [3]. The B-stage coating film according to item [1] or [2], further comprising (D) a water repellent. [4]. The B-stage coating film according to any one of items [1] to [3], wherein the coating material does not contain a thermal polymerization initiator. [5]. The B-stage coating film according to any one of items [1] to [4], wherein the (A) active energy ray-curable resin contains (A1) urethane (meth)acrylate. [6]. The B-stage coating film according to any one of items [1] to [5], wherein the (A) active energy ray-curable resin contains (A2) a copolymer of (a1) a multifunctional (meth)acrylate and (a2) a multifunctional thiol. [Explanation of symbols]

[0198] 1: Laminate having a dry coating on one side of a film substrate 2: Protective film 3: Rotating drum 4: Pressure roll 5: A laminate in which a protective film 2 is placed on the surface of the dried coating film of the laminate 1 and temporarily attached 6: Guide roll 7: B-stage coating laminated film 8:Heating device 9:Molding mold 10: Space between B-stage coating film laminate and molding die 11: Molded body

Claims

1. A method for producing a B-stage coating film, comprising the steps of: (1) forming a wet coating film on at least one surface of a film substrate using a coating material containing (A) an active energy ray-curable resin and (B) a photopolymerization initiator; (2) pre-drying the wet coating film formed in the step (1) to form a dry coating film; and (3) A step of autoclaving the dried coating film formed in the step (2) The above method comprising the steps of:

2. The method according to claim 1, further comprising the step of overlaying and temporarily attaching a protective film on the surface of the dried coating film formed in step (2) after step (2) and before step (3).

3. The method according to claim 1 or 2, wherein the autoclave treatment in the step (3) is carried out under conditions of a pressure of 0.15 to 1 MPa, a temperature of 23 to 100° C., and a time of 1 to 60 minutes.

4. The method according to any one of claims 1 to 3, further comprising a step of performing an aging treatment after the step (3).

5. The method according to any one of claims 1 to 4, wherein the coating further comprises (C) fine particles.

6. The method according to claim 5 , wherein the component (C) microparticles comprise microparticles that function as an antibacterial or antiviral agent.

7. The method according to any one of claims 1 to 6, wherein the coating further comprises (D) a water repellent.

8. The method according to any one of claims 1 to 7, wherein the coating is free of a thermal polymerization initiator.

9. The method according to any one of claims 1 to 8, wherein the (A) active energy ray curable resin contains (A1) urethane (meth)acrylate.

10. The method according to any one of claims 1 to 9, wherein the active energy ray curable resin (A) comprises (A2) a copolymer of (a1) a polyfunctional (meth)acrylate and (a2) a polyfunctional thiol.

11. The active energy ray-curable resin (A) contains (A1) a urethane (meth)acrylate and (A2) a copolymer of (a1) a polyfunctional (meth)acrylate and (a2) a polyfunctional thiol, The method according to any one of claims 1 to 10, wherein a blending ratio of the component (A1) to the component (A2) (mass of the component (A1) / mass of the component (A2)) is 93 / 7 to 40 / 60.

12. The method according to any one of claims 1 to 11, further comprising the step of transferring the autoclaved coating on the film substrate formed in step (3) onto a substrate other than the film substrate.

13. A method for producing a three-dimensional molded body, comprising the steps of: (P) obtaining a B-stage coating applied onto the film substrate or a B-stage coating transferred onto a substrate other than the film substrate by the method according to any one of claims 1 to 12; (Q) a step of imparting a three-dimensional shape to the B-stage coating film applied onto the film substrate obtained in the step (P), or the B-stage coating film transferred onto a substrate other than the film substrate; and (R) The above method, which includes a step of completely curing the B-stage coating film to which a three-dimensional shape has been imparted in the above step (Q).

Citation Information

Patent Citations

  • JP1975157437A

  • Method for forming inorganic cured coating layer

    JP1977152941A

  • Hard coating composition, multilayer sheet using the same, and method for manufacturing the same

    JP2012521476A

  • Film for processing, processed film, and method for producing them

    JP2016221922A

  • Hard coat laminate film

    JP2019151105A